Genetic variants in red blood cell adhesion-related genes influence the severity of sickle cell anemia in a malaria-endemic region - Irina Matos; Brígida Santos; Elisângela Gonçalves; Pedro Lopes; Miguel Brito; Ana Paula Arez; Paula Faustino (Molecular Biology Reports, 2026)
Background Sickle cell anemia (SCA) is a genetic disease marked by abnormal hemoglobin S and sickle-shaped red blood cells. It is highly prevalent in sub-Saharan Africa, especially in Angola, where SCA and malaria are major causes of childhood mortality. This study aimed to explore whether genetic variants in genes associated with red blood cell adhesion to the vascular endothelium influence the manifestations of SCA in Angolan pediatric patients in the context of malaria. Methods and results The study enrolled 65 pediatric SCA patients living in Luanda or Caxito. Their clinical, hematological, and biochemical profiles were monitored through longitudinal pediatric follow-up appointments. Fifteen polymorphic sites were genotyped in CD36 and ICAM-1 genes using PCR, Sanger sequencing, and fragment analysis by capillary electrophoresis. Malaria infection was evaluated by detecting Plasmodium species DNA through PCR analysis of blood spot samples. The CD36 variant rs3211891_C is revealed for the first time as a potential modulator of anemia severity in SCA. Additionally, the CD36 variant rs3211938_G, along with the ICAM-1 variants rs5491_T and rs5496_A, significantly impacted the severity of the hematological phenotype in SCA. Furthermore, SCA patients carrying the ICAM-1 rs5494_T variant showed a 5.63-fold increased risk of having malaria infection compared to those with the wild-type genotype. Conclusions This study enhances our understanding of genetic modifiers of red blood cell adhesion to the vascular endothelium and their influence on the severity of pediatric SCA in the context of frequent concomitant malaria infection in Angola.

Prevalence, antimicrobial resistance and detection of resistance genes of Escherichia coli and Salmonella spp. isolated from captive European wild boars reared in Brazil - Adriana Marques Faria; Itallo Conrado Sousa Araújo; Samantha Verdi Figueira; Maria Auxiliadora Andrade; Moema Pacheco Chediak Matos; Ana Maria de Souza Almeida; Guido Fontgalland Coelho Linhares (Archives of Microbiology, 2026)
The expansion of invasive European wild boar ( Sus scrofa scrofa ) populations in Brazil and the increasing commercialization of this species raise concerns about their role as reservoirs of zoonotic and antimicrobial-resistant bacteria. This study aimed to determine the prevalence, antimicrobial resistance profiles, and detection of virulence and resistance genes in Escherichia coli and Salmonella spp. isolated from captive wild boars. A total of 100 rectal swab samples were collected from animals raised on commercial farms in Goiás State, Brazil. One Salmonella isolate (1%) was detected and identified as serotype O:6,8, showing phenotypic resistance to ampicillin, amoxicillin, and sulfonamides, but no virulence or resistance genes were detected. E. coli was isolated from 56% of samples, with 98.2% of isolates classified as multidrug-resistant and all presenting antimicrobial resistance index values above 0.2. High resistance rates were observed for sulfonamides (96.8%), tetracycline (92.1%), amoxicillin (87.3%), ampicillin (85.7%), doxycycline (81.0%), whereas most isolates remained susceptible to ceftriaxone. Virulence genes were detected in a subset of isolates, including tsh (29.8%), papC (12.3%), and iss (7.0%), with some isolates presenting gene combinations associated with increased pathogenic potential. The eae gene was not detected, and no β-hemolytic activity was observed. These findings indicate a low occurrence of Salmonella but a high prevalence of multidrug-resistant and potentially pathogenic E. coli in captive wild boars, highlighting their potential role as reservoirs of antimicrobial resistance within a One Health context.

Movement of European freshwater mussels under simulated dewatering conditions - Ana Matos; Manuel Lopes-Lima; Paulo Castro; Luigi Fraccarollo; Janusz Golski; Sandra Kaźmierczak; Vanessa Modesto; Martin Österling; Sebastiano Piccolroaz; Ashkan Pilbala; Vincent Prié; Nicoletta Riccardi; et al. (Hydrobiologia, 2026)

Oceanographic parameters associated with spatial occurrence of cephalopods in standardized demersal fishing trawls in the NE Atlantic - Daniel Oesterwind; Anne Marie Power; Esther Abad; Gregoire Certain; Nikolaos Fotiadis; Alexey Golikov; Ángel F. González; Vladimir Laptikhovsky; Silvia S. Monteiro; Carlos Montero-Castaño; Ana Moreno; Hassan Moustahfid; et al. (Marine Biology, 2026)
In this work, the environmental occurrence ranges of different European cephalopod species are described for the whole NE Atlantic shelf including the greater North Sea and Baltic Sea. This is done based on the environmental parameters collected in-situ during surveys that caught commercially important cephalopod species (1990–2022). Results are supplemented and compared with information available in the published literature and are discussed in relation to available habitat across the range, survey design, etc., and, in particular, which species are most likely to be affected by climate change. Our analyses illustrate that Loligo forbesii occupies a broader depth range than Loligo vulgaris and Alloteuthis spp. Because L. forbesii occurs further offshore and at greater depths, this species is likely more resilient to warming than the other loliginids in our study. Octopus vulgaris is documented in areas close to the coast with a more southerly distribution, whereas Eledone cirrhosa occurs further north and further away from the coast. Eledone cirrhosa occurs at lower temperatures and has a much broader depth range, which may provide resilience against warming. By contrast, both ommastrephid squid species ( Illex coindetii and Todaropsis eblanae ) showed a very similar tolerance to the three environmental variables (salinity, temperature, depth). This information should contribute to future species distribution modelling by allowing validation of realistic results against each species’ range, habitat requirements, and environmental ranges, while appreciating the data limitations caused by the timing and gear used in the survey cruises that supply occurrence and density data.

Antibacterial effects of Lippia gracilis Schauer essential oil and its major compounds thymol and carvacrol against Acidovorax citrulli: Impacts on growth, biofilm formation, motility, and membrane permeability - Tamiris A.C. Santos; Ana Paula Alves Matos; Larissa de Souza Gois; Fabiany de Andrade Brito; Arie Fitzgerald Blank; Paulo Roberto Glagliardi; Roberta P.M. Fernandes (Biocatalysis and Agricultural Biotechnology, 2026)

The genus Pouteria: a review of advances in phytochemical elucidation and its pharmacological properties - Rafael C. Matos; Ana Flavia A. Bitencourt; Vanessa R. Prado; Alexsandro D. M. Oliveira; Renes R. Machado; Marina Scopel (Phytochemistry Reviews, 2026)
The genus Pouteria (family Sapotaceae) is traditionally used for gastrointestinal, inflammatory, and microbial issues, and has great nutritional applications because of the variety of fruits it contains. Despite its versatile applications, comprehensive research on Pouteria remains outdated, necessitating an integrative review of recent studies exploring its phytochemical evidence and biological activities. An unrestricted search in various databases (Jan/2009 to Aug/2022) focused on the genus “ Pouteria ”. Despite this genus having 325 recognized species, few studies have evaluated their bioactive potential, including antioxidant, anticancer, hypoglycemic, antimicrobial, anti-inflammatory, and antinociceptive, as well as their potential for treatment of Alzheimer disease. Regarding phytochemical evaluation, among the few substances isolated were a high number of terpenoids, flavonoids, phenolics, saponins, and others. In addition, owing to the high potential for fruit utilization, several primary metabolites were identified, which presented qualitative and quantitative diversity among species with the interests of the pharmaceutical industry. Therefore, this review provides information about phytochemical and pharmacological properties of the species of Pouteria . Given the shallow and incomplete results for several species, there is a demonstrated need for new studies encompassing all plant parts of Pouteria species, contributing to a more comprehensive understanding of their medicinal potential.

N-acetylcysteine mitigates oxidative stress and reduces alveolar bone damage on experimental periodontitis in rats - Ana Paula de Andrade Silva; Erick Alves dos Santos; Deborah Ribeiro Frazão; Vinicius Ruan Neves dos Santos; José Mario Matos-Sousa; Beatriz Risuenho Peinado; Deiweson Souza-Monteiro; Wallacy Watson Pereira Melo; Zuleni Alexandre da Silva; Everton Luiz Pompeu Varela; Jorddy Neves da Cruz; Carina Maciel da Silva-Boghossian; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
This study evaluated the effect of N-acetylcysteine ​​on oxidative biochemistry and bone damage during the development of ligature-induced experimental periodontitis in rats. The rats were divided into three groups (n = 8/group): control, experimental periodontitis (EP), or experimental periodontitis plus daily N-acetylcysteine administration (EP + NA) (100 mg/kg/day). Periodontitis was induced by bilateral silk ligatures on the mandibular first molars for 14 days. The antioxidant capacity of N-acetylcysteine ​​was measured by (2,2-azinobis [3-ethylbenzothiazoline-6-sulfonate] (ABTS• +) and 1,1-dipheny-2-picrylhydrazyl (DPPH•) assays. Gingival samples were collected for analysis of oxidative parameters, while mandibles were used for histopathological evaluations of inflammation and collagen content, as well as for micro-computed tomography assessments of bone quality and vertical bone loss. Data were analyzed by Analysis of Variance (ANOVA), Multivariate Analysis of Variance (MANOVA), and Pearson’s correlation ( p

Across climates and limits: a Brazil-Mediterranean benchmark of aflatoxins in peanuts and peanut butters - Juliano De Dea Lindner; Ana Carolina Ximenes Mesquita; Nicolò Fabulli; Ariane Mendonça Kluczkovski; Alessia Levante; Annalisa Ricci; Sonia Figuccia; Ângelo Paggi Matos; Marília Miotto; Valentina Bernini (Food Research International, 2026)

Synthesis and characterization of chitosan-functionalized nanostructured lipid carriers with temozolomide: cytotoxic effects and chromosomal instability in human glioblastoma cells - Helber Alves Negreiros; João Pedro Alves Damaceno do Lago; Victor Alves de Oliveira; Lia Raquel Alves Silva; Ana Carolina Lima de Melo; Igor Gabriel Barbosa de Sousa; Jefferson da Cruz Esteves; Sérgio Eduardo Matos Cazarotti Francisco; Samuel Lemos Paiva; João Pedro Crispim Guerra Rodrigues; Lucas Medeiros Martins Carvalho; Pedro Henricke Oliveira de Souza; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Multiform glioblastoma (GBM) is the most aggressive primary brain tumor, associated with high heterogeneity, treatment resistance, and poor survival. Temozolomide (TMZ), although the main chemotherapeutic agent used, shows limited efficacy due to low solubility, chemical instability, and acquired resistance. In this context, nanostructured systems can enhance their antitumor efficacy. This study aimed to develop and characterize chitosan-functionalized nanostructured lipid carriers loaded with Temozolomide (NLCTQ), as well as to assess their biological activity in human glioblastoma cells (U87-MG). Lipid nanoparticles functionalized with chitosan were prepared by hot emulsification and sonication. Physicochemical characterization included DLS, zeta potential, FTIR, and HPLC for drug quantification and encapsulation efficiency. Biological activity was evaluated in U87-MG cells using the cell viability assay MTT and trypan blue, the comet assay, the spheroid model, fluorescence cell death, and the CBMN assay. The formulation presented a homogeneous nanometric size and positive zeta potential, although with moderate encapsulation efficiency (39%). Biological assays demonstrated that NLCTQ significantly reduced cell viability, overcoming the U87-MG cell line’s resistance to TMZ by achieving cytotoxicity at doses up to 20 times lower than free TMZ. Additionally, NLCTQ promoted the formation of biomarkers of chromosomal instability, such as micronuclei, bridges, and nuclear buds, which may explain the observed cytotoxic effects. Together, the results indicate that TMZ nanoencapsulation in NLCTQ enhances its antitumor efficacy, representing a promising strategy to overcome the limitations of conventional chemotherapy in glioblastoma treatment.

Multidrug-resistant Pseudomonas aeruginosa in ICU patients and hospital surfaces: β-lactamase burden, biofilm formation and clonal spread - Marcos Eduardo Passos da Silva; Luccas Manoel de Melo Suica; Renata Santos Rodrigues; Márlon Grégori Flôres Custódio; Valcimar Batista Ferreira; Leilane da Silva Pontes; Ivson Cassiano de Oliveira Santos; Bruno Rocha Pribul; Núcia Cristiane da Silva Lima; Izabelly Vitória Gotara Ramos; Anjo Gabriel Carvalho; Mayra Gyovana Leite Belém; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Migration of ionic and nanoparticulate zinc from nanocellulose/ZnO nanoparticle films: morphology-dependent behaviour and modelling - Ana Rita Mendes; Otmar Geiss; Ivana Bianchi; Jessica Ponti; Ana Matos; Cristina L. M. Silva; Fátima Poças (Food Additives & Contaminants: Part A, 2026)

The first transcriptome of the diaphanous deep-sea hatchetfish Sternoptyx diaphana Hermann, 1781 (Teleostei: Sternoptychidae) - André Gomes-dos-Santos; Daniel Moita; David Barros-García; André M. Machado; Ana Matos; Nair Vilas-Arrondo; L. Filipe C. Castro; Elsa Froufe (Marine Genomics, 2026)

Green zero-valent iron nanoparticles from Cistus ladanifer by-products for glyphosate remediation in water and soil - Filipe Fernandes; Paula Paíga; Maria Freitas; Cláudia Pinho; Ana Isabel Oliveira; Cristina Delerue-Matos; Clara Grosso (Bioresource Technology, 2026)

Erector spinae plane block with bupivacaine contributes to intraoperative opioid sparing but provides limited postoperative pain control in cats undergoing elective ovariohysterectomy under continuous propofol infusion - Ana Paula Longo Ribeiro; Gilberto Serighelli-Júnior; Felipe Comassetto; Lorenzo Schmitz Borsato Cavagnari; Camila Fernanda Baehr Cavagnari; Atila Souza Rocha Freire de Santana; Maryana de Souza Matos; Ayla da Costa Wittaczik; Nilson Oleskovicz (Veterinary Research Communications, 2026)
This study evaluated the intraoperative and postoperative analgesic effects of an ultrasound-guided erector spinae plane (ESP) block with bupivacaine in cats undergoing elective ovariohysterectomy. Sixteen healthy client-owned female cats (with, 2.62 ± 0.46 kg; and, 23.06 ± 20.34 months) were randomly assigned to two groups ( n = 8 each). All animals received dexmedetomidine (2.5 µg/kg, intramuscularly), followed by propofol administered to effect for induction and maintained as a continuous rate infusion beginning at 0.3 mg/kg/min adjusted as necessary. Ultrasound-guided bilateral ESP blocks were performed at the first lumbar vertebra using 0.25% bupivacaine (0.5 mL/kg per side) in the bupivacaine group, (GB) or 0.9% saline in the saline group (GS). Intraoperative Cardiopulmonary variables and nociceptive responses were recorded, and fentanyl (2.5 µg/kg, IV) was administered as analgesia rescue. Postoperative pain was assessed over 24 h using the UNESP–Botucatu Multidimensional Pain Scale (short-form) and the Feline Grimace Scale, with buprenorphine rescue (20 µg/kg, IM). Cats in GB required fewer intraoperative fentanyl rescue (27 vs. 35 administrations), corresponding to a 22.85% reduction in total fentanyl rescue compared with the GS, however, no statistical difference between groups ( p = 0.5976). Intraoperative heart rate and systolic arterial pressure increased during periods of greater surgical stimulation in both groups, with no significant between-group differences. No significant differences were observed in postoperative requirement of analgesic rescue. ( p = 0.9554). These findings indicate that the ESP block with bupivacaine provides effective intraoperative opioid-sparing analgesia but limited postoperative benefit, supporting its use as part of a multimodal analgesic approach in feline abdominal surgery.

Concrete Jungle: habitat heterogeneity acts as environmental filter on multidimensional diversity of fruit-feeding butterflies in urban Savannahs of Cerrado biome - Geraldo de Brito Freire; Israel Pereira dos Santos Ribeiro; Ana Carolina Lacerda de Matos; Sofia Coradini Schirmer; Eduardo Guimarães Santos; Fernanda Vieira da Costa; Felipe M. Gawryszewski; Lee A. Dyer; Onildo J. Marini-Filho; Pedro Togni (Urban Ecosystems, 2026)

Mitochondrial Fumarase mRNA expression changes under Al stress in the genus secale and Brachypodium distachyon - Diaa Abd El-Moneim; Elisabete Santos; Roberto Contreras; Ana M. Figueiras; Manuela Matos; César Benito (Cereal Research Communications, 2026)

Metabolomics to target insecticidal compounds of Cenostigma pluviosum var. peltophoroides against Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) - João Luiz Baldim Zanin; Andréia Pereira Matos; Antônio Rogério Bernardo; Ana Carolina Volante; Daniele de Oliveira Silva; Danielle Ferreira Dias; João Henrique Ghilardi Lago; Daniela Aparecida Chagas-Paula; Marisi Gomes Soares (Natural Product Research, 2026)

Correction to: Comparative genomics of Sphingomonas from the cupuassu (Theobroma grandiflorum) phyllosphere reveals signatures of host adaptation and beneficial interactions - Ana Karla da Silva; Camila Henriques de Paula; Jéssica Pereira de Matos; Dilson Fagundes Ribeiro; Isabella Ferreira Cordeiro; Camila Gracyelle de Carvalho Lemes; Angélica Bianchini Sanchez; Camila Carrião Machado Garcia; Vinicius A. C. de Abreu; Rafael Moysés Alves; Mauro de Medeiros Oliveira; João Victor dos Anjos Almeida; et al. (Symbiosis, 2026)

Quantification of potentially toxic compounds in anhydrous cements: optimization of leaching by thermal analysis for sustainable production of cements - Bruna Souza Rosa; Samile Raiza Carvalho Matos; Luanne Bastos de Britto Barbosa; Heloysa Martins Carvalho Andrade; Ana Paula Kirchheim; Jardel Pereira Gonçalves (Environmental Science and Pollution Research, 2026)
The co-processing of waste in clinker synthesis is a widely adopted strategy to reduce the consumption of fossil fuels and natural raw materials. However, the incineration of waste may increase the release of potentially toxic compounds (PTCs) and volatile metals, raising concerns for the environment and human health. A major limitation in assessing these risks is the lack of suitable methods to directly quantify PTCs in anhydrous cement; existing approaches are typically limited to hydrated pastes. This study proposes a novel method for quantifying PTC in anhydrous cement by combining leaching tests and thermal analysis. The methodological framework involved: (i) identifying an acid solution capable of sustaining PTC quantification by prolonging reaction kinetics, (ii) selecting the leaching stage, and (iii) defining the optimal solid–liquid contact time. Portland cement samples were characterized, and the reactivity of different solutions was assessed by isothermal calorimetry prior to leaching tests. Results indicated that maintaining a pH between 0.65 and 0.70 optimizes the leaching solution, while the nitric acid/sodium hydroxide ratio must be adjusted explicitly for each cement type. Compared with the standard TCLP method, the proposed approach enabled the detection of 11 metals (Ba, Cr, Cu, Zn, Pb, Ni, La, V, Co, Sb, Mo, and Sn), demonstrating the effectiveness of the refined methodology.

Bisphenol S and high-fat diet drive structural and inflammatory remodeling of the colon in C57Bl/6 male mice - Beatriz Gouvêa de Luca; Beatriz Alexandre-Santos; Kauet de Matos Gama e Souza; Emanuelle Barreto-Reis; Ana Paula de Paula Alves; Thaís de Souza Carvalho-Laureano; Vinicius Sepúlveda-Fragoso; Luiza Gil Diniz; Milena Barcza Stockler-Pinto; Clarice Machado dos Santos; Denise Pires de Carvalho; Leandro Miranda-Alves; et al. (Toxicology Letters, 2026)

The KW18 peptide acts as a dual antimicrobial and immunomodulatory therapeutic candidate in the context of antimicrobial resistance - Layza Sá Rocha; Ana Cristina Jacobowski; Eduarda Thiburcio; Ana Paula de Araújo Boleti; Carolina Oliveira Matos; Juliana Bueno Barra; Luciano Morais Lião; Danieli Fernanda Buccini; Octávio Luiz Franco; Marlon Henrique Cardoso; Maria Ligia Rodrigues Macedo (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose Healthcare-associated infections and antimicrobial resistance present major challenges worldwide, especially for immunocompromised patients. This study aimed to evaluate the antimicrobial, antibiofilm, and immunomodulatory properties of KW18, a synthetic peptide (NH₂-KWIRRIIRRYVCFFRKFI-COOH) designed through bioinformatics to target multidrug-resistant bacteria and fungi, and to determine whether KW18 could serve as a dual-action therapy with potent microbicidal and anti-inflammatory effects. Methods KW18 was tested against Gram-positive and Gram-negative bacteria (Staphylococcus aureus, Pseudomonas aeruginosa) and fungi (Candida glabrata, C. tropicalis). MIC and MBC assays, time-kill curves, and checkerboard synergy tests were performed. Its antibiofilm activity was evaluated on mature biofilms. Membrane disruption was assessed using Sytox™ Green and ergosterol-binding assays. Immunomodulatory effects were analyzed in LPS-stimulated BV-2 microglial cells by measuring nitric oxide, IL-6, and IL-10 levels, and cytotoxicity was evaluated with cell viability assays. Results KW18 exhibited potent antimicrobial activity, with low MIC and MBC values across all strains, and retained antifungal effects even in the presence of ergosterol or sorbitol. Time-kill studies showed rapid, concentration-dependent microbicidal effects. The peptide worked synergistically with ciprofloxacin and amphotericin B, effectively inhibiting and eliminating mature biofilms and, in some cases, outperforming conventional treatments. Mechanistic tests confirmed membrane disruption. In BV-2 cells, KW18 reduced nitric oxide and IL-6 while increasing IL-10, all while maintaining over 85% cell viability, with a lower IC₅₀ for NO suppression than dexamethasone. Conclusion KW18 demonstrates strong antimicrobial, antibiofilm, and immunomodulatory activities, supporting its potential as a promising dual-function therapeutic candidate for resistant infections.

Ready to eat, ready to risk? A retrospective evaluation of microbiological contamination and surveillance gaps in self-service meals in Bahia, Brazil - Joselene C.N. Nascimento; Danilo M. Vilas-Boas; Clícia C. Leite; Victor O. Martinez; Juliana R. Matos; Mariana N. Roselino; Cleber A. Schmidt; Wilson J.F. Lemos Junior; Anderson S. Sant’Ana; Alaíse G. Guimarães (Food Control, 2026)

Molecular detection of medically relevant Sporothrix species in roadkilled wildlife in the Brazilian Atlantic forest - Steffanie Skau Amadei; Julia Campos; Andressa Maria Rorato Nascimento de Matos; Keity Aparecida Speçato; Eloiza Teles Caldart; Ana Paula Frederico Rodrigues Loure Bracarense; Ferry Hagen; Zoilo Pires de Camargo; Anderson Messias Rodrigues (Mycopathologia, 2026)
The rapid expansion of zoonotic sporotrichosis in South America necessitates innovative surveillance strategies to identify natural ecological niches. Roadkill provides a unique, underutilized opportunity to monitor Sporothrix circulation within human-impacted landscapes. We conducted a molecular survey via a triplex probe quantitative real-time PCR (qPCR) assay targeting pathogenic Sporothrix species in 81 roadkilled vertebrates (mammals, birds, and reptiles) collected along highways BR-376 and PR-445 traversing the Atlantic Forest in Paraná, Brazil (2017–2023). Genomic DNA from visceral organs (heart, liver, lung, and spleen) was screened for fungal DNA. Sporothrix DNA was detected in 13.6% (11/81) of the samples. Sporothrix schenckii predominated, identified in wild mammals ( Leopardus guttulus , Didelphis albiventris , and Lepus europaeus ) and diverse birds ( Colaptes melanochloros , Piaya cayana , and Selenidera maculirostris ), indicating systemic exposure. Strikingly, S. brasiliensis was detected in avian hosts ( Columbina picui , Crypturellus tataupa ), challenging the thermal-exclusion hypothesis and implicating birds as potential aerial vectors. Furthermore, S. globosa was found in Dasyprocta spp. and was co-detected with S. brasiliensis in Columbina picui . Notably, a reptile ( Oxyrhopus spp.) was positive for S. globosa and S. schenckii , expanding the known host spectrum, potentially via trophic transmission. Although distinguishing transient DNA carriage from active infection requires histopathological validation, these findings suggest that wildlife in fragmented corridors may function as reservoirs, biological amplifiers, or mechanical vectors rather than incidental hosts, reinforcing the blurring boundaries between sylvatic and synanthropic transmission cycles. In this context, integrating roadkill biosurveillance into a One Health framework is vital for tracking environmental pathogen loads and anticipating zoonotic spillover.

Comparative genomics of Sphingomonas from the cupuassu (Theobroma grandiflorum) phyllosphere reveals signatures of host adaptation and beneficial interactions - Ana Karla da Silva; Camila Henriques de Paula; Jéssica Pereira de Matos; Dilson Fagundes Ribeiro; Isabella Ferreira Cordeiro; Camila Gracyelle de Carvalho Lemes; Angélica Bianchini Sanchez; Camila Carrião Machado Garcia; Vinicius A. C. de Abreu; Rafael Moysés Alves; Mauro de Medeiros Oliveira; João Victor dos Anjos Almeida; et al. (Symbiosis, 2026)

Valorization of Water Hyacinth Biomass: Comprehensive Characterization and Production and Application of Activated Carbons - Ana Lourenço; Tiago Gomes; Maria Bernardo; Inês Matos; Nuno Lapa; Jorge Gominho (BioEnergy Research, 2026)
This study explored a potential route for valorizing the entire biomass from water hyacinth. Initially, the biomass underwent complete characterization, revealing high contents of ash (35%), extractives (25%), and monosaccharides (41%), with glucose being predominant (21%). Lignin content was low (19%), with a monomeric composition rich in G- and H-units (3.6% and 3.4%, respectively). The biomass exhibited a low calorific value (11 MJ/kg) and high oxygen content (62%), contrasted with low carbon values (31%) and high H/C (14.9) and O/C (1.9) ratios. Subsequently, biochar production was conducted at two temperatures (500 and 800 °C), where a high yield was obtained at 500 °C (44%). Three types of activated carbon were produced using different activation processes: physical activation with CO 2 and chemical activation with K 2 CO 3 and H 3 PO 4 . CO 2 activation yielded 34% but made almost no carbon or porosity (ABET = 9.4 m²/g). K 2 CO 3 activation produced carbons with a low yield (21%) but a very high surface area (862 m²/g), featuring micropores and mesopores. In contrast, H 3 PO 4 activation yielded 74%, resulting in primarily mesoporous material with minimal microporosity. The activated carbon produced with K 2 CO 3 demonstrated high removal efficiency for all the tested pharmaceutical compounds.

The chemical composition of Sargassum leachate reveals a potential threat to the aquifer of the Yucatan Peninsula, Mexico - Osorio-Montalvo Pedro Manuel; Ceja-Moreno Victor; Escalante-Mañé Ana Maribel; Aguilar-Medina Abel Antonio; Giácoman-Vallejos Germán; Nic-Matos José Germán; Peraza-Echeverria Santy; Canté-Loeza Freddy Lizandro; Puch-Hau Carlos Alberto (Marine Pollution Bulletin, 2026)

Chemical investigation, dereplication studies by UHPLC-ESI-HRMSMS/molecular networking, and antiproliferative activity of Symphyopappus cuneatus (Asteraceae) - Márcia R. P. Cabral; Carla Porto; Drielli R. Areas; Maria G. Matos; Debora C. Baldoqui; Marta R. B. Carmo; Mary A. Foglio; Mariana Cecchetto; Ana Lucia T. G. Ruiz; Maria H. Sarragiotto (Natural Product Research, 2026)

Rats, residues and rodenticide resistance: Hepatic concentration of anticoagulant rodenticides in genetically susceptible wild brown and black rats - Ana Carromeu-Santos; Beatriz Martín-Cruz; Tomé Neves; Elizandra Matos Cardoso; Naiara Guimarães Sales; Andrea Acosta Dacal; Ana Macías-Montes; Rita Pacheco; Bastiaan G. Meerburg; Allan D. McDevitt; Maria da Luz Mathias; Octavio Pérez Luzardo; et al. (Science of The Total Environment, 2026)

BK polyomavirus in a Portuguese healthy group: seroprevalence, viral Excretion, and implications for transmission pathways - Joana M. Oliveira; Daniela Veiga; Sara Pereira; Cristina Luxo; Ana Miguel Matos (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

First record of Phyllorhiza punctata von Lendenfeld, 1884 (Cnidaria: Rhizostomeae) in Portuguese waters: implications for regional marine ecosystems - Antonina dos Santos; Alexandra D. Silva; Pedro F. Silva; Ana Matos; Elsa Froufe (Marine Biodiversity, 2026)

Seamounts of Cabo Verde: A review of their ecological and economic significance, anthropogenic impacts, and conservation needs - Covadonga Orejas; Beatriz Vinha; Gillian B. Ainsworth; Sarah Saldanha; Teresa Militão; Christian Mohn; Thor H. Hansteen; Sara S. Ratão; Henk-Jan Hoving; Teresa Amaro; Dominique M.J. Anderson; Deusa Araújo; et al. (Progress in Oceanography, 2026)

Project Psyche: reference genomes for all Lepidoptera in Europe - Charlotte J. Wright; Niklas Wahlberg; Roger Vila; Marko Mutanen; Pável Matos-Maraví; Kay Lucek; Irena Kleckova; Leonardo Dapporto; Vlad Dincă; Claudia Bruschini; Christopher W. Wheat; Marta Vila; et al. (Trends in Ecology & Evolution, 2025)

3D electrochemical cork granule process for the removal of pharmaceuticals from urban wastewater - Paula V. Remor; Cristina Soares; Luísa Correia-Sá; Paula Paíga; Ana Rita Alves; Anita Pizzaia; Nuno Lapa; Elena Surra; Francisca C. Moreira; Vítor J.P. Vilar; Sónia A. Figueiredo; Cristina Delerue-Matos (Journal of Environmental Management, 2025)

Copper/zinc ratio and erythrocyte superoxide dismutase in patients with thyroid nodules - Bruna Aparecida Melo Batista; Matheus Aragão Dias Firmino; Paula Alexandre de Freitas; Morgana Pinheiro Sousa; Ana Carolina Marinho Ferreira; André Pires Cortez; Wladiana Oliveira Matos; Francisco Luan Fonsêca da Silva; Carla Soraya Costa Maia (BioMetals, 2025)

Use of microencapsulated pepper with different levels of energy supplementation in grazing beef cattle - Ana Paula Gonçalves Ferreira Miranda; Gleidson Giordano Pinto de Carvalho; Douglas dos Santos Pina; Leandro Soares Santos; Lara Maria Santos Brant; Paula Velozo Leal; Aureliano José Vieira Pires; Raiane Barbosa Mendes; Evandro Pereira Neto; Mirella Matos de Oliveira Xavier; Caio Seiti Takiya; José Esler de Freitas Júnior (Animal Feed Science and Technology, 2025)

Cordiaquinone B induces cytotoxicity and oxidative stress-mediated apoptosis in human colorectal cancer cells in vitro and in vivo - Stéphanie Aguiar de Negreiros Matos Silva; Fabrício dos Santos Machado; Luciano de Souza Santos; Maria Victoria Lima de Castro; Mateus Lima Nogueira; Milena Botelho Pereira Soares; Simone Alves Serafim Rocha; Renata Mendonça Araújo; Rosane Borges Dias; Daniel Pereira Bezerra; Ana Jérsia Araújo; José Delano Barreto Marinho Filho (Chemico-Biological Interactions, 2025)

Corrigendum to “Silver nanoparticles for control of foliar pathogens in passion fruit (Passiflora edulis) crops” [Biocatal. Agric. Biotechnol. 68 (2025) 103717] - Natália Deniz Brito; Rafael José Vilela de Oliveira; Felipe Leon Nascimento de Sousa; Ana Júlia Silva Rocha; Maria Eduarda Almeida Matos; Laura Lima Turani; Raphael Ferreira Queiroz; Bianca Galúcio Pereira Araújo; Giovanna Machado; Quelmo Silva de Novaes (Biocatalysis and Agricultural Biotechnology, 2025)

Uncovering the hidden underground associations of weeds with arbuscular mycorrhizal fungi and dark septate endophytes - Christiano da Conceição de Matos; Amarilson de Oliveira Cândido; Larissa Cassemiro Pacheco Monteiro; Jaqueline Maria do Nascimento; Lucia Ana Patricia Diaz Ariza; Francisco Cláudio Lopes Freitas; Maurício Dutra Costa (Phytoparasitica, 2025)

Here, There and Everywhere: Widespread Non‐Native Plants in the World's Urban Ecosystems - David M. Richardson; Lauren B. Trotta; Myla F. J. Aronson; Benjamin Baiser; Marc W. Cadotte; Marta Carboni; Laura Celesti‐Grapow; Sonja Knapp; Ingolf Kühn; Ana Carolina Lacerda de Matos; Zdeňka Lososová; Daijiang Li; et al. (Global Ecology and Biogeography, 2025)
Aim To (a) produce a list of the most widespread naturalised non‐native plant species across cities of the world; (b) explore whether cities on different continents are invaded by the same group of widespread naturalised species; and (c) elucidate the origins of the most widespread naturalised urban species. Location Global. Time Period No specific period. Major Taxa Studied Vascular plants. Method Using the most comprehensive and up‐to‐date dataset of non‐native urban floras yet assembled (GUBIC; Global Urban Biological Invasions Compendium), we identified the most widespread naturalised plant species (the global urban florome) by filtering for taxa present across all continents (except Antarctica) and their frequency in urban areas. To assess global patterns of urban plant naturalisation, we conducted ordination analyses and visualised species co‐occurrence. We also examined species origins and their environmental impact. Results Among the 7792 naturalised plant species recorded in 553 urban centres, 302 species (4%) were found on all six continents. Of these, 96 species, considered the most widespread species, were present in more than half of urban centres in Oceania, North America and South America; this proportion was higher than in Africa, Asia and Europe. Cities outside Europe and Asia are more homogeneous in terms of the species composition of the most widespread invaders. An analysis of species origins showed that temperate Asia contributed the most species globally, while intercontinental exchange patterns varied, with a notable one‐directional flow from North to South America. Main Conclusions Our results suggest that urban ecosystems outside Europe and Asia are more susceptible to recent invasions than those within these two continents. Understanding the composition and origins of these widespread species is crucial for developing coordinated management strategies and improving the resilience of urban biodiversity.

Hyperactive Otolith-Ocular Reflex During Heat Tilt (Rabbit’s Eye Sign) In Anti-Ma2 Rhombencephalitis - João Lemos; Sara Matos; Ana Inês Martins; João Durães; Alexandre Dionísio; Egídio Machado; André Jorge (The Cerebellum, 2025)

PKC-α activation with new semi-synthetic 7α-acetoxy-6β-hydroxyroyleanone derivatives for breast cancer therapeutics - Vera M. S. Isca; Ana C. Matos; Joana Almeida; Lucília Saraiva; Carlos A.M Afonso; Patrícia Rijo (Phytochemistry Letters, 2025)

Geopolymerization of fly ash: effect of sodium and potassium - Ana Laura Lopes de Matos Riscado; Carlos Maurício Fontes Vieira; Afonso Rangel Garcez de Azevedo; Markssuel Teixeira Marvila (Innovative Infrastructure Solutions, 2025)

Silver nanoparticles for control of foliar pathogens in passion fruit (Passiflora edulis) crops - Natália Deniz Brito; Rafael José Vilela de Oliveira; Felipe Leon Nascimento de Sousa; Ana Júlia Silva Rocha; Maria Eduarda Almeida Matos; Laura Lima Turani; Raphael Ferreira Queiroz; Bianca Galúcio Pereira Araújo; Giovanna Machado; Quelmo Silva de Novaes (Biocatalysis and Agricultural Biotechnology, 2025)

Unveiling the Secret: Effect of Grape Stems as Soil Amendments in Earthworm Tail Regeneration and Reproductive Success - Tiago Azevedo; Marta Roboredo; Ana I. R. N. A. Barros; Irene Gouvinhas; Lara Anjos; Rafael Araújo; João R. Sousa; Isabel Gaivão; Maria de Lurdes Pinto; Manuela Matos; Francisco Peixoto; Maria Manuel Oliveira; et al. (Journal of Soil Science and Plant Nutrition, 2025)
The increasing reliance on agricultural machinery to improve agronomic output and meet food demands disrupts soil structure and poses risks to soil biota, including mechanical injuries to earthworms. This study assesses the potential of grape stems as a soil amendment to promote earthworm regeneration and investigate their impact on reproduction and oxidative stress. Four experimental conditions were established: a control group (E0) with OECD reference soil and three groups where ground grape stems replaced 5% (E5), 10% (E10) and 25% (E25) of peat. Earthworms ( n = 10/replicate) were amputated 30 segments past the clitellum. Destructive sampling occurred at 15, 30, and 45 days post-amputation. Regenerated segments were measured/counted, while adjacent tissue and blastema were analysed for oxidative stress markers (catalase (CAT), glutathione S-transferase (GST), peroxidase (POD), superoxide dismutase (SOD) activities). Reproductive output was assessed 60 days post-amputation. Regeneration outcomes revealed a nuanced relationship with grape stem amendments, demonstrating non-lethal effects and enhanced reproduction at certain concentrations. However, higher grape stem percentages (E25) revealed a slight delay in regeneration. Grape stem exposure induced changes in antioxidant enzyme activities, particularly in detoxification mechanisms mediated by GST and POD, with distinct activity levels observed in blastema and adjacent tissues. Grape stems as soil amendments demonstrate potential benefits for earthworm health, including improved reproduction and modulated oxidative stress responses. However, optimal application rates are crucial to avoid adverse effects on regeneration. These findings highlight the dual role of soil amendments in nutrient provision and promoting the well-being of soil organisms. Graphical Abstract

Coconut shell derived activated carbon for effective separation of greenhouse gases - Julio E. Sosa; Rui.P.P.L. Ribeiro; Inês Matos; Maria Bernardo; Isabel M. Fonseca; José P.B. Mota; João M.M. Araújo; Ana B. Pereiro (International Journal of Refrigeration, 2025)

Can early weaning in the previous lactation of beef cows affect the metabolism and postnatal development of female offspring? - Thiago Kan Nishimura; Matheus Sousa de Paula Carlis; Ana Clara Degan Matos; Isabella Rio Feltrin; Rodrigo Silva Goulart; Germán Darío Ramírez Zamudio; Saulo Luz Silva; Arlindo Saran Netto; Paulo Roberto Leme; Guilherme Pugliesi (Tropical Animal Health and Production, 2025)

Ecotoxicity of the non-dioxin-like PCB-153 in the model marine diatom Phaeodactylum tricornutum - Bernardo Duarte; João Cardoso; Eduardo Feijão; João Albuquerque Carreiras; Ricardo Cruz de Carvalho; Ana Rita Matos; Vanessa F. Fonseca; Paula Santos; Carla Palma (Journal of Hazardous Materials, 2025)

Non-chromatographic inorganic arsenic speciation in rice by spectrophotometry using silver nanoparticles as platform sensor - Francisco Eduardo Holanda Lima; Francisco Luan Fonsêca da Silva; Abdullah Abkar Akhdhar; Pierre Basílio Almeida Fechine; Ana Rita de Araujo Nogueira; Wladiana Oliveira Matos (Food Chemistry, 2025)

Microalgae extracts reduce appetite in zebrafish larvae linked to long-chain fatty acids and 5′-methylthioadenosine - Javier Sanz Moxó; Ana Catarina Fonseca; Gabriela Matos; Jorge Saraiva; Ricardo Pereira; Cristina Rocha; Vítor Vasconcelos; Ralph Urbatzka (Algal Research, 2025)

Do (xeno)estrogens pose a risk to earthworms? Soy isoflavones and estradiol impact gonad structure and induce oxidative stress in Eisenia fetida - Tiago Azevedo; Rita Silva-Reis; Beatriz Medeiros-Fonseca; Mariana Gonçalves; Gabriel Mendes; Marta Roboredo; Maria J. Rocha; Francisco Peixoto; Maria de Lurdes Pinto; Manuela Matos; João R. Sousa; Paula A. Oliveira; et al. (Chemosphere, 2025)

Water quality for bivalve molluscs and consumer safety: Application of novel and adapted multimetric indices in a coastal lagoon system exposed to wastewater discharges - Alexandra Cravo; Ana B. Barbosa; Maria João Lima; Cristina Ferreira; Cátia Correia; André Matos; José Jacob; Sandra Caetano (Marine Pollution Bulletin, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Anatomical, histochemical, and micromorphological aspects of leaf gall in Myrciaria floribunda H.West ex Willd. O. Berg (Myrtaceae) - Luan Gonçalves Castilho; Naiara Viana Campos; Sabrina Dias de Matos; Tatiana Ungaretti Paleo Konno; Mariana Aparecida de Almeida Souza; Ana Cláudia de Macêdo Vieira (Flora, 2025)

Efficacy of a formulation of chlorfenvinphos and dichlorvos on Rhipicephalus microplus in vivo test in Bahia, Brazil - Aline Kelly Araújo Costa Velame Ferreira; Wagner Carvalho e Silva Neto; Igor de Castro Oliveira; Maria Clara Bastos Rodrigues; Ângela Cristina de Oliveira Lima; Tiago Velame Ferreira; Carolina Carneiro de Matos; Ana Karina da Silva Cavalcante; Lorendane Millena de Carvalho; Wendell Marcelo de Souza Perinotto (Tropical Animal Health and Production, 2025)

Hydrological signatures in Brazilian catchments: a machine learning approach for spatial estimates - Gustavo de Oliveira Correa; Francisco Eustáquio Oliveira e Silva; Ana Clara de Sousa Matos (Hydrological Sciences Journal, 2025)

Regulation of the Caribbean red snapper fishery on the Amazon continental shelf: 60 years of conflict between conservation and exploitation - Alex Garcia Cavalleiro de Macedo Klautau; Rafael Anaisce das Chagas; Paulo Emílio Costa Santos; Bruno Barbosa Iespa; Israel Hidenburgo Aniceto Cintra; Ana Patricia Barros Cordeiro; Wagner Cesar Rosa dos Santos; Jose Augusto Negreiros Aragão; Carlos Eduardo Matos Carvalho Bastos; Flávio de Almeida Alves-Junior; Beatrice Padovani Ferreira; Bianca Bentes da Silva (Marine Policy, 2025)

Exploring the potential of lipid elicitors to enhance plant immunity - Gonçalo Laureano; Ana Rita Matos; Andreia Figueiredo (Progress in Lipid Research, 2025)

Impact chains for the deep seafloor: assessing pressures footprint under limited knowledge and uncertainty - Fábio L. Matos; Ana Hilário; Heliana Teixeira (Frontiers in Marine Science, 2025)
Pressures on the marine environment threaten biodiversity, ecosystem functions and services. Current marine environmental policies, such as the European Marine Strategy Framework Directive, require the assessment of combined effects and the application of ecosystem-based management approaches to maintain or achieve Good Environmental Status (GES) of marine ecosystems. We mapped the major activities and pressures affecting deep-sea benthic habitats in the mainland component of the Portuguese EEZ to assess their combined effects and support decision-making on management and conservation. Activities related to marine traffic, fisheries, and climate change processes are among the most prevalent in the study area. As a data-poor case study, most of the pressure layers were only partially mapped due to a lack of information or the inadequacy of the available data on activities to derive suitable proxies of pressure intensity. Pressures related to chemical changes, chemicals and other pollutants were the most widespread, while abrasion and damage were the most geographically limited. Endogenic pressures dominate in bathyal benthic habitats and decrease their prevalence with depth, while exogenic pressures are more widespread in the abyss than in the bathyal area. Benthic habitats in the bathyal zone, closer to the 200-meter bathymetric contour, consistently exhibited higher combined effect scores, suggesting higher risk of potential impacts on these ecosystem components. Research directed towards these areas is required to assess the state of these habitats and develop conservation and restoration measures, if necessary, to achieve GES. A continuous support for open-access databases containing high-quality, standardized, and harmonized marine data is crucial for future assessments of the combined effects of human pressures on deep-sea ecosystems.

Molecular detection of respiratory viruses: an observational study on respiratory co-infections in children and adults - Tereza de Jesus Pinheiro Gomes Bandeira; Ana Leticia Sousa de Oliveira; Luis Fernando Pontes Martins; Rodrigo Moreira Matos; Sheryda Raynna Nobre Guedes dos Santos; Mateus Cedro Lopes; Raimundo Tadeu Pires Sobreira; Hermano Alexandre Lima Rocha (Brazilian Journal of Microbiology, 2025)

Conserving saproxylic flagship species by complementing 150 years of natural history with citizen science data—the case of the stag beetles (Lucanidae, Coleoptera) of Portugal - João Gonçalo Soutinho; João Carvalho; Milene Matos; José Manuel Grosso-Silva; Tatiana C. Moreira-Pinhal; Carla Rego; Sónia Ferreira; João Gonçalo Abreu; Ana Rita Gonçalves; Helena Ceia; Carlos Fonseca; Cristina Rufino; et al. (Biodiversity and Conservation, 2025)
The use of flagship species in conservation, such as the European Stag Beetle ( Lucanus cervus), can positively affect the conservation of other taxonomic or functionally related species. This is especially true for taxonomic groups where the knowledge regarding their distribution and ecology is generally limited, as is the case of insects. This work represents the most accurate and up-to-date publication on the distribution, ecology and environmental niche of the four lucanids found in Portugal. Moreover, it unravels how citizen science initiatives can positively impact conservation planning for flagship species and their taxonomic and functionally related species. Compared to non-citizen science sources, citizen science data increased the known distribution area for all four species (1.6 to 7.2 fold) and confirmed most of the current known species distribution (50.0% to 95.5%). It also expanded the known environmental niche breadth for all species (1.1 to 4.2 fold) and the species suitable modelled habitat (1.1 to 2.1 fold) with very good model performances (AUC > 0.8 and TSS > 0.6). Our results suggest that to improve the conservation of these species, it is paramount to value native forests in Portugal. Management actions to accomplish this might include preserving current native forests and small natural features (such as large old trees) throughout the landscape while simultaneously increasing native forest development. In addition, climate change will affect the species' distribution since all are highly susceptible to specific (bio-)climatic conditions that are expected to change in the next decades. These findings not only enhance our understanding of these species' current distribution but also pave the way for targeted and integrative conservation efforts throughout the country, especially in areas where the (now assessed) ecological niche requirements and habitat availability (either in terms of landscape composition or structure) are met. Guidelines and priorities are discussed on how to implement conservation measures in Portugal following the recently approved European Nature Restoration Law.

Assessing the impact of TiO2 nanomaterials on intestinal cells: New evidence for epithelial translocation and potential pro-inflammatory effects - Dora Rolo; Joana F.S. Pereira; Lídia Gonçalves; Ana Bettencourt; Peter Jordan; Maria João Silva; Paulo Matos; Henriqueta Louro (Toxicology, 2025)

Addressing the urgent climate and biodiversity crisis through strategic ecosystem restoration in Brazil - Luisa Fernanda Liévano-Latorre; Juliana M. de Almeida-Rocha; Alberto Akama; Hernani Alves Almeida; Ricardo Teixeira Gregório Andrade; Marcelo Rodrigues dos Anjos; Yasmine Antonini; Thaise de Oliveira Bahia; Flavia Rodrigues Barbosa; Reinaldo Imbrozio Barbosa; Claudia Franca Barros; Helena Godoy Bergallo; et al. (Biological Conservation, 2025)

HiDaFernPT : Historical data of spore availability for 121 fern and lycopod taxa in Portugal (1926–2013) - Sérgio Timóteo; Ruben Heleno; Filipe Covelo; Joaquim Santos; Pedro Lopes; António C. Gouveia; Arménio Matos; Agostinho Salgado; M. Teresa Girão da Cruz; João Farminhão; Marta Horta; Guilherme Barreto; et al. (Ecology, 2025)
Species phenology is being altered by ongoing climate changes with yet underappreciated consequences for ecological processes and ecosystem stability. Contrary to what happens with some key life events of flowering plants, comparatively little information exists about fern and lycophyte phenology and how it is affected by the current climatic changes. In part, this stems from the lack of long‐term datasets. Here we provide information on the collection day and site of the spores of 121 native and introduced fern (Polypodiopsida) and lycopod (Lycopodiopsida) taxa for the Index Seminum of the Botanic Garden of the University of Coimbra. Spores were collected from spontaneous and cultivated individuals across Portugal between 1926 and 2013. The database includes 3383 curated records with information on the species, or infraspecific taxa (including authority), and are fully georeferenced and provided with a confidence interval for the collection site. Taxonomy was first curated manually by in‐house botanists and then harmonized according to the Global Biodiversity Information Facility (GBIF) backbone taxonomy. The data are released under a Creative Commons Attribution Non Commercial (CC‐BY‐NC 4.0) license.

Breeding-induced changes in the rhizosphere microbial communities in Lima bean (Phaseolus lunatus) - Karla Annielle da Silva Bernardo Brito; Sandra Mara Barbosa Rocha; Ângela Celis de Almeida Lopes; Verônica Brito Silva; Regina Lucia Ferreira Gomes; Carlos Humberto Aires Matos Filho; Arthur Prudêncio de Araujo Pereira; Vania Maria Maciel Melo; Erika Valente de Medeiros; Lucas William Mendes; Ana Roberta Lima de Miranda; Ademir Sérgio Ferreira Araujo (Applied Soil Ecology, 2025)

Halophila baillonii's hidden distribution range: Rediscovery and conservation of a rare seagrass in the Tropical Atlantic - Karine Matos Magalhães; Thomaz Henrique Arruda Lima; Roberto Lima Barcellos; Ana Maria Costa Souza (Aquatic Botany, 2025)

Cooling storage of collared peccary (Pecari tajacu) semen at different temperatures - Romário Parente dos Santos; Ana Gloria Pereira; Yuri Gonçalves Matos; Gabriel Santos Costa Bezerra; Lilian Leal Dantas; Alexandre Rodrigues Silva (Animal Reproduction Science, 2025)

Exploring acylated anthocyanin-based extracts as a natural alternative to synthetic food dyes: Stability and application insights - Ana Rita Pereira; Virgínia Cruz Fernandes; Cristina Delerue-Matos; Victor de Freitas; Nuno Mateus; Joana Oliveira (Food Chemistry, 2024)

B-mode, Doppler, and Elastography abdominal ultrasound in Tamandua tetradactyla - Rafael Kretzer Carneiro; Ana Sofia Matos; Rafaela Della Giustina; Kaio Augusto dos Santos; Bárbara Corbellini Rovaris; Igor Cezar Kniphoff da Cruz; Aury Nunes de Moraes (Veterinary Research Communications, 2024)

Phenotypic variation seems not to be associated with the genetic profile in Zygopetalum (Orchidaceae): a case study of a high-elevation rocky complex - Shaiany Sabrina Lopes Gomes; Juliana Mainenti Leal Lopes; Elyabe Monteiro de Matos; Elisa Guimarães Cabral; Ana Luisa Sousa Azevedo; Marco Antonio Machado; José Marcello Salabert de Campos; Luiz Menini Neto; Lyderson Facio Viccini (Molecular Biology Reports, 2024)

From cactus to crop: genomic insights of a beneficial and non-pathogenic Curtobacterium flaccumfaciens strain and the evolution of its pathosystem - Dilson Fagundes Ribeiro; Jéssica Pereira de Matos; Lorrana Cachuite Mendes Rocha; Ana Karla da Silva; Camila Henriques de Paula; Isabella Ferreira Cordeiro; Camila Gracyelle de Carvalho Lemes; Angélica Bianchini Sanchez; Camila Carrião Machado Garcia; João Carlos Setubal; Robson Francisco de Souza; Alessandro de Mello Varani; et al. (Molecular Genetics and Genomics, 2024)

Diversity and potential functional role of phyllosphere-associated actinomycetota isolated from cupuassu (Theobroma grandiflorum) leaves: implications for ecosystem dynamics and plant defense strategies - Jéssica Pereira de Matos; Dilson Fagundes Ribeiro; Ana Karla da Silva; Camila Henriques de Paula; Isabella Ferreira Cordeiro; Camila Gracyelle de Carvalho Lemes; Angélica Bianchini Sanchez; Lorrana Cachuite Mendes Rocha; Camila Carrião Machado Garcia; Nalvo F. Almeida; Rafael Moyses Alves; Vinicius A. C. de Abreu; et al. (Molecular Genetics and Genomics, 2024)

Hepatitis E virus prevalence among HIV-2 infected individuals in central Portugal - João Pereira-Vaz; Anália Carmo; Vítor Duque; Cristina Luxo; Ana Alves; Alexandra Mendes; Célia Morais; Cláudio Gaspar; Raquel Costa; Lurdes Correia; Fernando Rodrigues; Ana Matos (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Magnesium, selenium and zinc deficiency compromises antioxidant defense in women with obesity - Ana Raquel Soares de Oliveira; Kyria Jayanne Clímaco Cruz; Jennifer Beatriz Silva Morais; Loanne Rocha dos Santos; Stéfany Rodrigues de Sousa Melo; Larissa Cristina Fontenelle; Juliana Soares Severo; Jéssica Batista Beserra; Thayanne Gabryelle Visgueira de Sousa; Suelem Torres de Freitas; Emyle Horrana Serafim de Oliveira; Carla Soraya Costa Maia; et al. (BioMetals, 2024)

Aqueous extract of Spirulina exerts neuroprotection in an experimental model of Alzheimer sporadic disease in mice induced by Streptozotocin - Juliete Tavares; Alfaete Vieira Oliveira; Tyciane de Souza Nascimento; Jessica Maria Pessoa Gomes; Ana Caroline Barros Parente; Jessica Rabelo Bezerra; Mac Dionys Rodrigues da Costa; Mayara Sandrielly Soares de Aguiar; Tiago Lima Sampaio; Francisco Arnaldo Viana Lima; Glauce Socorro de Barros Viana; Geanne Matos de Andrade (Metabolic Brain Disease, 2024)

The use of water in wineries: A review - Cristina Matos; Manuela Castro; José Baptista; António Valente; Ana Briga-Sá (Science of The Total Environment, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

The impact of plant-based product denomination on consumer expectations and sensory perception: A study with vegan chocolate dessert - Alexandre Henrique Silas Souza; Katiúcia Alves Amorim; Louise Paiva Passos; Maria Laura Silva Galdino; Júlia Fernanda Urbano Marinho; Juliana Santos Marques; Karen Lendengue de Matos Regalado; Ana Carla Marques Pinheiro (Food Research International, 2024)

Diving into the metabolic interactions of titanium dioxide nanoparticles in “Sparus aurata” and “Ruditapes philippinarum” - Mário Jorge Araújo; María Vazquez; Laura Rodriguez-Lorenzo; Antonio Moreda-Piñeiro; Elza Fonseca; Natalia Mallo; Ivone Pinheiro; Monica Quarato; Elizabeth Bigorra-Ferré; Ana Matos; Aldo Barreiro-Felpeto; Maria V. Turkina; et al. (Environmental Pollution, 2024)

Evolution and Plasticity of Gene Expression Under Progressive Warming in Drosophila subobscura - Marta A. Antunes; Marta A. Santos; Ana S. Quina; Mauro Santos; Margarida Matos; Pedro Simões (Molecular Ecology, 2024)
Understanding the molecular mechanisms of thermal adaptation is crucial to predict the impacts of global warming. However, there is still a lack of research on the effects of rising temperatures over time and of studies involving different populations from the same species. The present study focuses on these two aspects, which are of great importance in understanding how organisms cope and adapt to ongoing changes in their environment. This study investigates the impact of global warming on the gene expression patterns of Drosophila subobscura populations from two different latitudinal locations after 23 generations of evolution. Our results indicate that evolutionary changes depend on the genetic background of the populations, with different starting points for thermal evolution, and that high‐latitude populations show more pronounced evolutionary changes, with some evidence of convergence towards low‐latitude populations. We found an interplay between plasticity and selection, with the high‐latitude population showing fewer initial plastic genes and lower levels of adaptive plasticity, but a greater magnitude of change in both plastic and selective responses during evolution under warming conditions compared with its low‐latitude counterpart. A substantial proportion of the transcriptome was observed to be evolving, despite the lack of observable response at higher‐order phenotypic traits. The interplay between plasticity and selection may prove to be an essential component in shaping species’ evolutionary responses to climate change. Furthermore, the value of conducting studies on multiple populations of the same species is emphasised, given the identification of differences between populations with different backgrounds in several contexts.

Antimicrobial and anthelmintic effects of copper nanoparticles against Koi carp parasites and their toxicity - Gracienhe Gomes dos Santos; Liseth Vanessa Perengue Riofrio; Ana Paula Sousa; Paola Capistrano Santos; Alexandre Vaz Silva; Emilly Monteiro Lopes; Domickson Silva Costa; Jucimauro de Araújo Pereira Júnior; Giulia Beatrice Ferreira; Graziella Vivine Gonçalves de Matos Silva; Marilia Tedesco; Diego José Nogueira; et al. (Journal of Fish Diseases, 2024)
This study investigated the in vitro antimicrobial and anthelmintic effect of copper nanoparticles (CuNPs) against the bacterium Aeromonas hydrophila , the monogeneans Dactylogyrus minutus , Dactylogyrus extensus , Gyrodactylus cyprini , and the cestode Schyzocotyle acheilognathi , as well as their toxicity to Cyprinus carpio Koi. In the antimicrobial in vitro test, the inhibition zone method and minimum inhibitory concentration (MIC) were performed. In order to determine the time and efficacy of monogenean parasite mortality, the parasites were exposed to CuNP concentrations of 20, 50, 100, 150, 200, and 300 mg L −1 , and a control group with tank water and one with copper sulphate pentahydrate (CuSO 4 . 5 H 2 O) at a concentration of 0.3 mg L −1 , performed in triplicate. The parasites were observed every 10 min for 300 min, and mortality was recorded. For the cestodes, parasites were immersed in CuNP concentrations of 50, 100, 150, and 300 mg L −1 . At the end of the in vitro tests, the anthelmintic efficacy of each treatment was calculated. To assess the tolerance and toxicity in fish, they were exposed to CuNP concentrations of 0.6, 1.25, 2.5, 5, 10, 20, and 50 mg L −1 for 12 h. The MIC demonstrated that CuNPs effectively inhibited the growth of A . hydrophila up to a dilution of 12,500 mg L −1 and showed an inhibition zone of 14.0 ± 1.6 mm for CuNPs. The results of anthelmintic activity showed a dose‐dependent effect of concentration for both groups of parasites, with the most effective concentration being 300 mg L −1 in 120 min. In the toxicity test, the carps showed tolerance to lower concentrations. The study indicated that CuNPs were effective against the studied pathogens. However, it proved to be toxic to fish at high concentrations. The use of low concentrations is recommended still requires further investigation.

Influence of Dolphin-Watching Tourism Vessels on the Whistle Emission Pattern of Common Dolphins and Bottlenose Dolphins - Ana A. Silva; Joana Castro; André Cid; Sérgio M. Jesus; Fábio L. Matos (Oceans, 2024)
Recent years have seen a notable rise in dolphin-watching boat activities along the Algarve coast in Portugal, potentially affecting the common dolphin (Delphinus delphis) and bottlenose dolphin (Tursiops truncatus) local populations. This study examines the impact of increasing underwater noise levels from these boats on dolphin vocalizations. Field recordings were conducted from June to September 2022, analyzing dolphin whistles in various boat presence scenarios. The results indicate significant changes in whistle-frequency characteristics with boat presence, including increased start, low, and high frequencies, alongside a decrease in the number of inflection points in modulated whistles. The changes might negatively impact dolphin populations viability, underscoring the need for further research. Additionally, improved mitigation strategies may be necessary to reduce the potential negative effects of dolphin watching on cetacean communication and behavior in the Algarve region.

Portuguese macroalgae and halophytes for human consumption: Minimal risk of norovirus and Salmonella infection - Joana M. Oliveira; Miguel A. Pardal; Leonel Pereira; Ana M. Matos; Elsa T. Rodrigues (Food Control, 2024)

Habitat permeability drives community metrics, functional traits, and herbivory in neotropical spontaneous urban flora - Wanda Karolina da Silva; Ana Carolina Lacerda de Matos; Rafael Dudeque Zenni (Flora, 2024)

SARS-CoV2 Nsp1 is a metal-dependent DNA and RNA endonuclease - Bruno A. Salgueiro; Margarida Saramago; Mark D. Tully; Federico Issoglio; Sara T. N. Silva; Ana C. F. Paiva; Cecília M. Arraiano; Pedro M. Matias; Rute G. Matos; Elin Moe; Célia V. Romão (BioMetals, 2024)
Over recent years, we have been living under a pandemic, caused by the rapid spread of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV2). One of the major virulence factors of Coronaviruses is the Non-structural protein 1 (Nsp1), known to suppress the host cells protein translation machinery, allowing the virus to produce its own proteins, propagate and invade new cells. To unveil the molecular mechanisms of SARS-CoV2 Nsp1, we have addressed its biochemical and biophysical properties in the presence of calcium, magnesium and manganese. Our findings indicate that the protein in solution is a monomer and binds to both manganese and calcium, with high affinity. Surprisingly, our results show that SARS-CoV2 Nsp1 alone displays metal-dependent endonucleolytic activity towards both RNA and DNA, regardless of the presence of host ribosome. These results show Nsp1 as new nuclease within the coronavirus family. Furthermore, the Nsp1 double variant R124A/K125A presents no nuclease activity for RNA, although it retains activity for DNA, suggesting distinct binding sites for DNA and RNA. Thus, we present for the first time, evidence that the activities of Nsp1 are modulated by the presence of different metals, which are proposed to play an important role during viral infection. This research contributes significantly to our understanding of the mechanisms of action of Coronaviruses.

Quality and microstructure of tilapia fillets (Oreochromis niloticus) subjected to different freezing methods - Karen Lendengue de Matos Regalado; Kelly Lendengue de Matos Regalado; Francielly Corrêa Albergária; Ana Luiza de Souza Miranda; Maria Emília de Sousa Gomes; Jaime Vilela de Resende (International Journal of Refrigeration, 2024)

Exploring the potential of biomass-derived carbons for the separation of fluorinated gases with high global warming potential - Julio E. Sosa; Rui P.P.L. Ribeiro; Inês Matos; Maria Bernardo; Isabel M. Fonseca; José P.B. Mota; João M.M. Araújo; Ana B. Pereiro (Biomass and Bioenergy, 2024)

MYCOLICIBACTERIUM FORTUITUM INFECTION IN EX SITU EMERALD TREE BOA (Corallus batesii) - Cássia Regina Ramos Gonzaga; Flora Nogueira Matos; Mayara Grego Caiaffa; Maraya Lincoln Silva; Rodrigo Hidalgo Friciello Teixeira; Eduardo Ferreira-Machado; Ticiana Brasil Ervedosa; Pedro Enrique Navas-Suárez; Rodrigo Albergaria Ressio; Cinthya dos Santos Cirqueira; Ketlyn Bolsachini Figueiredo; Ana Carolina Souza Ramos de Carvalho; et al. (Brazilian Journal of Microbiology, 2024)

Do endocrine disrupting compounds impact earthworms? A comprehensive evidence review - Tiago Azevedo; Mariana Gonçalves; Rita Silva-Reis; Beatriz Medeiros-Fonseca; Marta Roboredo; João R. Sousa; Paula A. Oliveira; Maria de Lurdes Pinto; Francisco Peixoto; Isabel Gaivão; Manuela Matos; Ana M. Coimbra (Reviews in Environmental Science and Bio/Technology, 2024)
Endocrine-disrupting compounds (EDCs) are ubiquitous in soil, posing serious risks to soil biota, especially earthworms, which have been found to be affected by these compounds, despite not being their typical target organisms. Earthworms are essential for sustaining soil health and quality, by promoting soil aeration, organic matter decomposition and nutrient cycling, among other functions. This review synthesizes available literature evidencing the negative impact of EDC exposure, through traditional endocrine pathways and other toxicological mechanisms, on histopathological, biochemical, molecular and reproductive endpoints of earthworms. The compounds described, in the consulted literature, to induce histopathological, biochemical, genotoxicity and molecular and reproductive alterations include antibiotics, antimicrobial additives, flame retardants, fragrances, fungicides, herbicides, hormones, inorganic ions, insecticides, organic UV filters, parabens, perfluoroalkyl substances, pesticides, petroleum derivatives, plasticizers and polychlorinated biphenyls. These compounds reach soil through direct application or via contaminated organic amendments and water derived from potentially polluted sources. The findings gather in the present review highlight the vulnerability of earthworms to a broad spectrum of chemicals with endocrine disrupting capacity. Additionally, these studies emphasize the physiological disruptions caused by EDC exposure, underscoring the critical need to protect biodiversity, including earthworms, to ensure soil quality and ecosystem sustainability. Ongoing research has provided insights into molecular mechanisms responsive to EDCs in earthworms, including the identification of putative hormone receptors that exhibit functional similarity to those present in vertebrates. In conclusion, this review emphasizes the impact of EDCs in earthworms, especially through non-hormonal mediated pathways, and addresses the need for strong regulatory frameworks to mitigate the detrimental effects of EDCs on soil invertebrates in order to safeguard soil ecosystems. Graphical abstract

Connecting the Brazilian Vertical System to the International Height Reference Frame by estimating the vertical datum parameters - Gabriel do Nascimento Guimarães; Ana Cristina Oliveira Cancoro de Matos; Denizar Blitzkow (Journal of South American Earth Sciences, 2024)

Bayesian estimation of hydrological model parameters in the signature-domain: Aiming for a regional approach - Ana Clara de Sousa Matos; Francisco Eustáquio Oliveira e Silva (Journal of Hydrology, 2024)

Molecular evidence of sporadic Coxiella burnetii excretion in sheep milk, central Portugal - Humberto Pires; Sérgio Santos-Silva; Andreia V.S. Cruz; Luís Cardoso; Ana Patrícia Lopes; Maria A. Pereira; Carmen Nóbrega; Ana Cristina Mega; Carla Santos; Rita Cruz; Fernando Esteves; Helena Vala; et al. (Veterinary Research Communications, 2024)
Coxiella burnetii is the etiologic agent of Q fever, a worldwide zoonosis. Cattle, sheep and goats are considered the main reservoirs of the disease. Transmission to humans occurs mainly through the inhalation of infectious aerosols from milk, faeces, urine, and birth products from infected ruminants. In this study, a 2-year longitudinal approach was performed to ascertain the excretion of C. burnetii in bulk tank milk samples of sheep from a mountain plateau in central Portugal, with sampling conducted during the years 2015 and 2016. From a total of 156 bulk tank milk samples tested by qPCR, only one showed to be positive for C. burnetii (1.28% [95%CI: 0.03–6.94]), from 2015, the first year of collection. Bidirectional sequencing and phylogenetic analysis of IS1111 transposase partial region confirmed the presence of C. burnetii DNA. The presence of C. burnetii in raw milk samples highlights the necessity for additional research to determine if raw milk is a potential source for human infection. Animal health surveillance and prevention measures against this zoonotic disease should be considered.

Relationship Between Zinc, Selenium, and Magnesium Status and Markers of Metabolically Healthy and Unhealthy Obesity Phenotypes - Kyria Jayanne Clímaco Cruz; Ana Raquel Soares de Oliveira; Larissa Cristina Fontenelle; Jennifer Beatriz Silva Morais; Stéfany Rodrigues de Sousa Melo; Loanne Rocha dos Santos; Thayanne Gabryelle Visgueira de Sousa; Suelem Torres de Freitas; Gilberto Simeone Henriques; Silvana Bordin; Carla Soraya Costa Maia; Francisco Erasmo de Oliveira; et al. (Biological Trace Element Research, 2024)

Invasive non-native species in Brazil: an updated overview - Rafael D. Zenni; Sílvia R. Ziller; Clarissa A. da Rosa; Rafael B. Sühs; Patricia B. Puechagut; Beloni T. P. Marterer; Gustavo Heringer; Ana Carolina L. de Matos; Marina L. Bueno; Jonathan W. Almeida; Carlos H. T. Silva; José Renato Legracie-Júnior; et al. (Biological Invasions, 2024)

Correction to: The net-tube caddisflies (Trichoptera: Psychomyioidea: Xiphocentronidae) from the Brazilian Amazon: discovery of new species and reports of new distributional records - Gleison R. Desidério; Albane Vilarino; Laissa S. Santos; Marcos A. R. Pires; Ana M. Pes; Talissa Matos; Karina Dias-Silva; Neusa Hamada (Biologia, 2024)

Efficient carbamazepine removal from wastewater using a continuous three-dimensional electro-Fenton system at natural pH - Antón Puga; Cristina Soares; Ana Cruz del Álamo; M. Isabel Pariente; Raúl Molina; Fernando Martínez; M. Angeles Sanromán; Marta M. Pazos; Cristina Delerue-Matos (Journal of Water Process Engineering, 2024)

Ultrasound-assisted extraction of bioactive compounds from goji berries: Optimization, bioactivity, and intestinal permeability assessment - Filipa Teixeira; Ana Margarida Silva; Stefania Sut; Stefano Dall'Acqua; Oscar L. Ramos; Alessandra B. Ribeiro; Ricardo Ferraz; Cristina Delerue-Matos; Francisca Rodrigues (Food Research International, 2024)

Nonthermal high-pressure microalgae extracts: A new source of natural ingredients for cosmetics - Mónica P. Garcia; Ana Regueiras; Graciliana Lopes; Gabriela Matos; Lucília P. da Silva; Mariana T. Cerqueira; Helena Cardoso; Nádia Correia; Jorge A. Saraiva; Joana L. Silva; Rosário Martins; Alexandra P. Marques (Algal Research, 2024)

Organic stabilization and methane production under different organic loading rates in UASB treating swine wastewater - Jacineumo Falcão de Oliveira; Ronaldo Fia; Ana Flavia Santos Rabelo de Melo; Fátima Resende Luiz Fia; Fernando Neris Rodrigues; Luciene Alves Batista Siniscalchi; Mateus Pimentel de Matos (Biodegradation, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

The net-tube caddisflies (Trichoptera: Psychomyioidea: Xiphocentronidae) from the Brazilian Amazon: discovery of new species and reports of new distributional records - Gleison R. Desidério; Albane Vilarino; Laissa S. Santos; Marcos A. R. Pires; Ana M. Pes; Talissa Matos; Karina Dias-Silva; Neusa Hamada (Biologia, 2024)

Assessing water storage variations in La Plata basin and sub-basins from GRACE, global models data and connection with ENSO events - Ayelen Pereira; Cecilia Cornero; Ana Cristina Oliveira Cancoro de Matos; Rafael Seoane; María Cristina Pacino; Denizar Blitzkow (Hydrological Sciences Journal, 2024)

Transcriptome profiling of the posterior salivary glands of the cuttlefish Sepia officinalis from the Portuguese West coast - Cátia Gonçalves; Inês Moutinho Cabral; António P. Alves de Matos; Ana R. Grosso; Pedro M. Costa (Frontiers in Marine Science, 2024)
Cephalopods like octopuses and cuttlefishes are known to secrete a ‘toxic saliva’ to inject into their prey, especially crustaceans since the XIX century. However, only in the mid-XX century were the first coleoid-specific toxins successfully isolated. Motivated by the growing interest on the global ocean as an almost inexhaustible source of novel bioactive compounds, we used RNA-Seq – based transcriptomics and de novo assembly of transcriptomes to screen the posterior salivary glands of Sepia officinalis (the common cuttlefish) from the Portuguese West coast for toxins and other bioactive proteins and peptides. Supported by microanatomical analyses, the posterior salivary glands constitute indeed the ‘venom gland’ whereas the more elusive anterior salivary glands (embedded in the buccal mass) are responsible for the production of mucin-rich saliva that is effectively the vehicle that transports the toxins as the venom is injected into the prey. Indeed, the transcriptomic profiling suggests that the cuttlefish venom is complex mixture of bioactive proteins, among which neurotoxins are major players, together with enzymes whose function is to digest the extracellular matrix to facilitate diffusion of the toxins. Nonetheless, by comparing with previous RNA-Seq data obtained from S. officinalis collected from other biogeographical areas, it may be suggested that significant inter-populational variation in venom composition can occur, which may potentially increase the span of bioactives secreted by these animals. We isolated and validated the full coding sequences for three important toxins, a cysteine-rich venom protein (CRVP), a venom insulin (VIns) and a cephalotoxin (CTX). The toxins seem to be relatively conserved among coleoids but diverging from other venomous mollusks such as cone snails. Their properties as potent modulators of glucose (in the case of VIns) and as potential neurotoxins (like CRVP and CTX) can render them primer targets for drug development.

Association of β-globin polymorphisms and tolerance to haemonchosis in ewes and lambs of different sheep breeds - Rafaela Tami Ikeda Kapritchkoff; Cintia Hiromi Okino; Simone Cristina Méo Niciura; Hornblenda Joaquina Silva Bello; Renata Silva Matos; Glaucia Roberta Melito; Flavia Aline Bressani; Sérgio Novita Esteves; Ana Carolina de Souza Chagas (Veterinary Parasitology, 2024)

Energy efficiency in winemaking industry: Challenges and opportunities - Manuela de Castro; José Baptista; Cristina Matos; António Valente; Ana Briga-Sá (Science of The Total Environment, 2024)

Comparison between commercial media and TRIS-egg yolk extender in the refrigerated storage of collared peccary semen at 17 °C - Romário P. Santos; Samara S.J. Moreira; Luana G.P. Bezerra; Yasmim C.S. Cavalcante; Ana G. Pereira; Tayná M. Matos; Moacir F. Oliveira; Alexandre R. Silva (Animal Reproduction Science, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Ascorbic acid mediated mitigation of drought effects on growth, physiology, and essential oil profile in culantro (Eryngium foetidum L.) - Sabrina Kelly dos Santos; Daniel da Silva Gomes; Vanessa de Azevedo Soares; Estephanni Fernanda Oliveira Dantas; Ana Flávia Pellegrini de Oliveira; Moises Henrique Almeida Gusmão; Elyabe Monteiro de Matos; Lyderson Facio Viccini; Richard Michael Grazul; Juliane Maciel Henschel; Diego Silva Batista (Vegetos, 2024)

Can exposure to lisdexamfetamine dimesylate from juvenile period to peripubertal compromise male reproductive parameters in adult rats? - Julia Stein; Bárbara Campos Jorge; Lívia Trippe Nagaoka; Ana Carolina Casali Reis; Beatriz de Matos Manoel; Alana Rezende Godoi; Vanessa Caroline Fioravante; Francisco Eduardo Martinez; Patrícia Fernanda Felipe Pinheiro; André Sampaio Pupo; Arielle Cristina Arena (Toxicology and Applied Pharmacology, 2024)

Effects of redox modulation on quiescin/sulfhydryl oxidase activity of melanoma cells - Ester Mazepa; Ana Luiza Dorigan de Matos Furlanetto; Hulyana Brum; Lia Sumie Nakao; Pierina Alexandra Martinez; Silvia Maria Suter Correia Cadena; Maria Eliane Merlin Rocha; Elizabeth Sousa Cunha; Glaucia Regina Martinez (Molecular and Cellular Biochemistry, 2024)

Comparative responses and effects of exposure to metallic and nanoparticle zinc in the mussel Mytilus galloprovincialis - Joana Roma; Madalena Missionário; Carolina Madeira; Ana Rita Matos; Catarina Vinagre; Pedro M. Costa; Bernardo Duarte (Estuarine, Coastal and Shelf Science, 2024)

Novel insights into enzymes inhibitory responses and metabolomic profile of supercritical fluid extract from chestnut shells upon intestinal permeability - Diana Pinto; Julián Lozano-Castellón; Ana Margarida Silva; María de la Luz Cádiz-Gurrea; Antonio Segura-Carretero; Rosa Lamuela-Raventós; Anna Vallverdú-Queralt; Cristina Delerue-Matos; Francisca Rodrigues (Food Research International, 2024)

Enhancing the taxonomic delimitation of Lippia origanoides Kunth (Verbenaceae) by analyzing volatile terpenes and molecular markers in micropropagated accessions - Laís M. Frattini; Arthur A. Oliveira; Jhoão S. Kotsubo; Íris B. Gorne; Isabel C. Silva; Jober C. E. Freitas; Cristiano F. Resende; Ana C. Mezzonato-Pires; Elyabe M. Matos; Juliana M. L. Lopes; Lyderson F. Viccini; Richard M. Grazul; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

How complex is the hidden species diversity of the teleost Plotosus genus? - Elsa Froufe; André Gomes-dos-Santos; Ana Matos; Jonathan Wilson; Salman Malakpourkolbadinezhad; Daniel D. Pereira; Randal Singer; L. Filipe C. Castro (Ichthyological Research, 2024)
The striped eel catfish, Plotosus lineatus was first described by Thunberg in 1787 from the Indo-Pacific region in the East Indian Ocean. Since then, the species has been recorded in various marine and brackish habitats in Japan, southern Korea, the Ogasawara Islands, Australia, Lord Howe Island, Palau and Yap in Micronesia, East Africa to Samoa, Madagascar, Red Sea and the Persian Gulf. Occurrences of this species have also been registered in the Mediterranean Sea, a non-native location, indicating a possible biological invasion event. Despite its long history, the taxonomic status of the P. lineatus species complex remains puzzling and uncertain. Here, we analysed all the available mitochondrial cytochrome c oxidase subunit 1 sequences (NCBI and BOLD) from specimens covering the current known distribution range, in an attempt to clarify the evolutionary relationships of different lineages within this species. We deduce nine monophyletic Lineages - I–IX , of P. lineatus with Kimura-2P distances ranging from 2% to 16%, with a mean intraspecific distance of 6%. Strikingly, Lineage V is composed uniquely of Mediterranean-captured individuals, with an unknown evolutionary origin. These findings strongly suggest the need for a careful species taxonomic reassessment. Some Lineages are composed of individuals from specific geographic locations (e.g., Australia and Indonesia), while others include specimens from broader geographic areas (e.g., almost all Indo-Pacific coastline). Additionally, several deposited sequences are most likely the result of morphology-based misidentifications. Due to the biological invasive potential, as well as the use of the species as a valuable physiology model, the P. lineatus species complex requires further attention. Overall our study offers a clear framework for future comparative studies of striped eel catfish individuals captured from different ecosystems.

Influence of incompatible pollen grains on the reproductive success of Ipomoea asarifolia (Desr.) Roem. & Schult. (Convolvulaceae) in Restinga, RN, Brazil - Bruna Yvila Melo Santos; Karine de Matos Costa; Natan Messias de Almeida; Maria Teresa Buril; André Maurício Melo Santos; Ana Virgínia Leite (Brazilian Journal of Botany, 2023)

What influences consumer food waste in urban households? Guidelines for communication strategies in Portugal - Joana Simões; Tânia Pinto-Varela; Margarida Gaspar de Matos; Ana Carvalho (Journal of Cleaner Production, 2023)

An improved reference genome and first organelle genomes of Quercus suber - Ana Usié; Octávio Serra; Pedro M. Barros; Pedro Barbosa; Célia Leão; Tiago Capote; Tânia Almeida; Leandra Rodrigues; Isabel Carrasquinho; Joana B. Guimarães; Diogo Mendoça; Filomena Nóbrega; et al. (Tree Genetics & Genomes, 2023)
Cork oak ( Quercus suber L.) is an ecologically and economically important evergreen tree species native to the Mediterranean region and widespread in southwest Europe and northwest Africa. An improved genome assembly of cork oak using a combination of Illumina and PacBio sequencing is presented in this study. The assembled genome contains 2351 scaffolds longer than 1000 bp, accounting for 765.7 Mbp of genome size, L90 of 755, and a N50 of 1.0 Mbp, with 40,131 annotated genes. The repetitive sequences constitute 53.6% of the genome. The genome sequences of chloroplast and mitochondrion were determined for the first time, with a genome size of 161,179 bp and 531,858 bp, respectively. Phylogenetic analysis based on complete chloroplast genome sequence showed that Q. suber is closely related to Quercus variabilis , two cork-producing species with commercial use. All data generated are available through the public databases, being ready to be used without restrictions. This study provides an improved nuclear genome assembly together with the organelle genomes of cork oak. These resources will be useful for further breeding strategies and conservation programs and for comparative genomic studies in oak species.

Predictors for Prolonged Hospital Stay Solely to Complete Intravenous Antifungal Treatment in Patients with Candidemia: Results from the ECMM Candida III Multinational European Observational Cohort Study - Matthias Egger; Jon Salmanton-García; Aleksandra Barac; Jean-Pierre Gangneux; Hélène Guegan; Valentina Arsic-Arsenijevic; Tadeja Matos; Rok Tomazin; Nikolai Klimko; Matteo Bassetti; Helena Hammarström; Eelco F. J. Meijer; et al. (Mycopathologia, 2023)
Background To date, azoles represent the only viable option for oral treatment of invasive Candida infections, while rates of azole resistance among non-albicans Candida spp. continue to increase. The objective of this sub-analysis of the European multicenter observational cohort study Candida III was to describe demographical and clinical characteristics of the cohort requiring prolonged hospitalization solely to complete intravenous (iv) antifungal treatment (AF Tx). Methods Each participating hospital (number of eligible hospitals per country determined by population size) included the first ~ 10 blood culture proven adult candidemia cases occurring consecutively after July 1st, 2018, and treating physicians answered the question on whether hospital stay was prolonged only for completion of intravenous antifungal therapy. Descriptive analyses as well as binary logistic regression was used to assess for predictors of prolonged hospitalization solely to complete iv AF Tx. Findings Hospital stay was prolonged solely for the completion of iv AF Tx in 16% (100/621) of candidemia cases by a median of 16 days (IQR 8 – 28). In the multivariable model, initial echinocandin treatment was a positive predictor for prolonged hospitalization to complete iv AF Tx (aOR 2.87, 95% CI 1.55 – 5.32, p < 0.001), while (i) neutropenia, (ii) intensive care unit admission, (iii) catheter related candidemia, (iv) total parenteral nutrition, and (v) C. parapsilosis as causative pathogen were found to be negative predictors (aOR 0.22 – 0.45; p < 0.03). Interpretation Hospital stays were prolonged due to need of iv AF Tx in 16% of patients with candidemia. Those patients were more likely to receive echinocandins as initial treatment and were less severely ill and less likely infected with C. parapsilosis .

Measuring healthy ageing: current and future tools - Nádia Silva; Ana Teresa Rajado; Filipa Esteves; David Brito; Joana Apolónio; Vânia Palma Roberto; Alexandra Binnie; Inês Araújo; Clévio Nóbrega; José Bragança; Pedro Castelo-Branco; Raquel P. Andrade; et al. (Biogerontology, 2023)
Human ageing is a complex, multifactorial process characterised by physiological damage, increased risk of age-related diseases and inevitable functional deterioration. As the population of the world grows older, placing significant strain on social and healthcare resources, there is a growing need to identify reliable and easy-to-employ markers of healthy ageing for early detection of ageing trajectories and disease risk. Such markers would allow for the targeted implementation of strategies or treatments that can lessen suffering, disability, and dependence in old age. In this review, we summarise the healthy ageing scores reported in the literature, with a focus on the past 5 years, and compare and contrast the variables employed. The use of approaches to determine biological age, molecular biomarkers, ageing trajectories, and multi-omics ageing scores are reviewed. We conclude that the ideal healthy ageing score is multisystemic and able to encompass all of the potential alterations associated with ageing. It should also be longitudinal and able to accurately predict ageing complications at an early stage in order to maximize the chances of successful early intervention.

Prevention, protocols, and lab capacity: lessons from a norovirus outbreak in the Algarve - Regina Sá; Joana Roque; Pedro Marques Mendes; Inês Gonçalves; Judite Sousa; Cátia Matos; Álvaro Júnior; Anabela Coelho; Cristina Belo Correia; Vera Manageiro; Corrado Minetti; Rita de Sousa; et al. (Archives of Virology, 2023)

Feature-Based Place Recognition Using Forward-Looking Sonar - Ana Rita Gaspar; Aníbal Matos (Journal of Marine Science and Engineering, 2023)
Some structures in the harbour environment need to be inspected regularly. However, these scenarios present a major challenge for the accurate estimation of a vehicle’s position and subsequent recognition of similar images. In these scenarios, visibility can be poor, making place recognition a difficult task as the visual appearance of a local feature can be compromised. Under these operating conditions, imaging sonars are a promising solution. The quality of the captured images is affected by some factors but they do not suffer from haze, which is an advantage. Therefore, a purely acoustic approach for unsupervised recognition of similar images based on forward-looking sonar (FLS) data is proposed to solve the perception problems in harbour facilities. To simplify the variation of environment parameters and sensor configurations, and given the need for online data for these applications, a harbour scenario was recreated using the Stonefish simulator. Therefore, experiments were conducted with preconfigured user trajectories to simulate inspections in the vicinity of structures. The place recognition approach performs better than the results obtained from optical images. The proposed method provides a good compromise in terms of distinctiveness, achieving 87.5% recall considering appropriate constraints and assumptions for this task given its impact on navigation success. That is, it is based on a similarity threshold of 0.3 and 12 consistent features to consider only effective loops. The behaviour of FLS is the same regardless of the environment conditions and thus this work opens new horizons for the use of these sensors as a great aid for underwater perception, namely, to avoid degradation of navigation performance in muddy conditions.

Using satellite data to estimate the evapotranspiration in Brazilian basins: From 2003 to 2016 - Samuel Rodrigues da Cunha; Gabriel do Nascimento Guimarães; Ana Cristina Oliveira Cancoro de Matos (Remote Sensing Applications: Society and Environment, 2023)

Insights from the maternal lineage of the F2 generation after exposure to an environmentally relevant dose of benzo(a)pyrene in the male rats of F0 generation - Bárbara Campos Jorge; Julia Stein; Ana Carolina Casali Reis; Beatriz de Matos Manoel; Lívia Trippe Nagaoka; Arielle Cristina Arena (Environmental Science and Pollution Research, 2023)

First morphological and molecular isolation of Talaromyces marneffei in beech marten (Martes foina) in Portugal - Ana Cristina Matos; Catarina Jota Baptista; Paula A. Oliveira; Ana Sofia Soares; Luís Figueira; Manuela Matos; Ana Cláudia Coelho (Research in Veterinary Science, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Paternal low-dose benzo(a)pyrene exposure in rats impairs sexual development and fertility of the paternal lineage in F2 generation: A transgenerational study - Bárbara Campos Jorge; Julia Stein; Ana Carolina Casali Reis; Jéssica Nogueira Bueno; Beatriz Rizzo Paschoalini; Suyane da Silva Moreira; Beatriz de Matos Manoel; Arielle Cristina Arena (Toxicology, 2023)

Thymol and eugenol against Rhipicephalus sanguineus sensu lato engorged females: Biological, histopathological and bioinformatic analysis - Isabela Santos Silva; Letícia Vale; Ana Lúcia Coutinho; Lainny Jordana Martins Pereira e Sousa; Paula Marchesini; Renata da Silva Matos; Luís Adriano Anholeto; Maria Izabel Camargo Mathias; Lorena Lopes Ferreira; Walquiria Arruda; Caio Monteiro (Veterinary Parasitology, 2023)

A metagenomics approach to characterize the footrot microbiome in Merino sheep - Ana Usié; Célia Leão; Daniel Gaspar; Helena Monteiro; Lino Tábuas; Elisa Bettencourt; Pedro Caetano; Ludovina Padre; Nuno Carolino; António Marcos Ramos; Claudino de Matos; Sandra Branco (Veterinary Microbiology, 2023)

Musa spp. cultivars as a neutralising source against some toxic activities of Bothrops and Crotalus genus snake venoms - Márcia Matos da Silva; Gerso Pereira Alexandre; Marta Regina Magalhães; Ana Maria Torres; Lucilia Kato; Victória Costa da Silva; Simone Maria Teixeira de Saboia Morais; Armando Garcia Rodriguez; Taícia Pacheco Fill; Alana Kelyene Pereira; Jussara Roque; Jorge Luiz Souza Simão; et al. (Toxicon, 2023)

Ezrin immunoexpression in trophoblast cells of the equine placenta - Isabela Syllos Campos; Bárbara Paula Dos Santos Batista; Ana Carina Heil Silva Matos; Juliana Da Silva Leite; Gustavo Mendes Gomes; Letícia Patrão De Macedo Gomes; Aline Emerim Pinna; Ana Maria Reis Ferreira (Journal of Equine Veterinary Science, 2023)

Magnetic solid phase extraction as a nonchromatographic method for the quantification of ultratrace inorganic arsenic in rice by inductively coupled plasma-optical emission spectrometry (ICP OES) - Francisco L.F. da Silva; Francisco E.H. Lima; Davino M. Andrade Neto; Fernando L. de Menezes; Lillian M.U.D. Fechine; Abdullah Akhdhar; Livia P.D. Ribeiro; Ana R.A. Nogueira; Pierre B.A. Fechine; Gisele S. Lopes; Wladiana O. Matos (Food Chemistry, 2023)

Valorisation of spent tire rubber as carbon adsorbents for Pb(II) and W(VI) in the framework of a Circular Economy - Maria Bernardo; Nuno Lapa; Filomena Pinto; Miguel Nogueira; Inês Matos; Márcia Ventura; Ana Maria Ferraria; Ana Maria Botelho do Rego; Isabel Maria Fonseca (Environmental Science and Pollution Research, 2023)
Spent tire rubber-derived chars and their corresponding H 3 PO 4 and CO 2 -activated chars were used as adsorbents in the recovery of Pb(II) ion and (W(VI)) oxyanion from synthetic solutions. The developed chars (both raw and activated) were thoroughly characterized to have insight about their textural and surface chemistry properties. H 3 PO 4 -activated chars presented lower surface areas than the raw chars and an acidic surface chemistry which affected the performance of these samples as they showed the lowest removals of the metallic ions. On the other hand, CO 2 -activated chars presented increased surface areas and increased mineral content compared to the raw chars, having presented higher uptake capacities for both Pb(II) (103–116 mg/g) and W(VI) (27–31 mg/g) ions. Cation exchange with Ca, Mg and Zn ions was appointed as a mechanism for Pb removal, as well as surface precipitation in the form of hydrocerussite (Pb 3 (CO 3 ) 2 (OH) 2 ). W(VI) adsorption might have been ruled by strong electrostatic attractions between the negatively charged tungstate species and the highly positively charged carbons’ surface. The results shown in this work allow concluding that the valorisation of spent tire rubber through pyrolysis and the subsequent activation of the obtained chars is an alternative and a feasible option to generate adsorbent materials with a high uptake capacity of critical metallic elements.

DNA metabarcoding to assess prey overlap between tuna and seabirds in the Eastern tropical Atlantic: Implications for an ecosystem-based management - Ana Rita Carreiro; Jaime A. Ramos; Vanessa A. Mata; Nathalie M. Almeida; Isabel Rodrigues; Ivo dos Santos; Diana M. Matos; Pedro M. Araújo; Teresa Militão; Jacob González-Sólis; Vitor H. Paiva; Ricardo Jorge Lopes (Marine Environmental Research, 2023)

First assessment of leaf lipids and fatty acids as biomarkers of grapevine tolerance/susceptibility to Plasmopara viticola - Ana Rita Cavaco; Gonçalo Laureano; Bernardo Duarte; Jorge Marques da Silva; Carla Gameiro; Jorge Cunha; José Eiras Dias; Ana Rita Matos; Andreia Figueiredo (Physiological and Molecular Plant Pathology, 2023)

Impact of anthropogenic noise on the survival and development of meagre (Argyrosomus regius) early life stages - Rita Trabulo; M. Clara P. Amorim; Paulo J. Fonseca; Manuel Vieira; André B. Matos; Thibaut Marin-Cudraz; Marco F.L. Lemos; Ariana B. Moutinho; Sara C. Novais; Pedro Pousão-Ferreira; Ana Candeias-Mendes; Ana M. Faria (Marine Environmental Research, 2023)

Assessment of Habitat Suitability for Common Cockles in the Ria the Aveiro Lagoon Under Average and Projected Environmental Conditions - Fábio L. Matos; Nuno Vaz; Ana Picado; João M. Dias; Francisco Maia; Miguel B. Gaspar; Luísa Magalhães (Estuaries and Coasts, 2023)

Past history shapes evolution of reproductive success in a global warming scenario - Marta A. Santos; Marta A. Antunes; Afonso Grandela; Ana Carromeu-Santos; Ana S. Quina; Mauro Santos; Margarida Matos; Pedro Simões (Journal of Thermal Biology, 2023)

Potential of rainwater harvesting in the retail sector: a case study in Portugal - Ana Ferreira; Vitor Sousa; Manuel Pinheiro; Inês Meireles; Cristina Matos Silva; Jorge Brito; Ricardo Mateus (Environmental Science and Pollution Research, 2023)
Water is a crucial resource for life, and it is increasingly scarce in many regions of the globe. In addition, retail water use is responsible for up to 19% of public water globally supplied. Hence, this study has set out to explore the technical and economic feasibility of rainwater harvesting systems as an alternative water source for a retail store located in southern Portugal. Water consumption data from 2018 to 2021 was collected from water bills, placing average monthly water consumption at around 400 m 3 . Next, rainfall data was collected from the nearest meteorological station, comprising 54 years of daily rainfall data between 1932 and 2008 with an annual average of 685 mm. The simulation of a rainwater harvesting system was performed, resorting to the mass-balance model. The optimal tank size was found to be 100 m 3 considering simply the relation with the relative water savings variation on the graph relating the water savings with the tank size. Results show that the simulated rainwater harvesting system would allow saving 32–36% of the water consumed, despite the store’s location in a dry climate, representing a financial gain of €330–372 per month. Findings suggest a substantial potential for the technical and economic feasibility of rainwater systems in retail stores, which makes them relevant solutions to achieve important water-savings in the retail sector, thus positively influencing retailers’ direct water footprint.

Pesticidal activity of Cratyllia mollis seed lectin preparation (cramoll 1,2,3) against the termite Nasutitermes corniger and mite Tetranychus bastosi - Yasmin Bruna de Siqueira Bezerra; Carlos Romero Ferreira de Oliveira; Leonardo Prezzi Dornelles; Caio César da Silva Guedes; Ana Patrícia Silva de Oliveira; Luana Cassandra Breitenbach Barroso Coelho; Cláudia Helena Cysneiros Matos de Oliveira; Gabriel Alves dos Santos; Thiago Henrique Napoleão; Thâmarah de Albuquerque Lima; Patrícia Maria Guedes Paiva (Crop Protection, 2023)

Safety evaluation of ondansetron after gestational exposure on male reproductive parameters in rats - Ana Carolina Casali Reis; Bárbara Campos Jorge; Julia Stein; Suyane da Silva Moreira; Beatriz de Matos Manoel; Ariana Musa Aquino; Leticia Cardoso Valente; Cândida Aparecida Leite Kassuya; Wellerson Rodrigo Scarano; Arielle Cristina Arena (Regulatory Toxicology and Pharmacology, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Sexual segregation in the foraging distribution, behaviour, and trophic niche of the endemic Boyd’s shearwater (Puffinus lherminieri boydi) - Ivo dos Santos; Jaime A. Ramos; Filipe R. Ceia; Isabel Rodrigues; Nathalie Almeida; Stefan Antunes; Ana R. Carreiro; Diana M. Matos; Ricardo J. Lopes; Pedro Geraldes; Vítor H. Paiva (Marine Biology, 2022)

Substitution of urea–formaldehyde by renewable phenolic compound for environmentally appropriate production of particleboards - Ana Carolina Corrêa Furtini; Flávia Maria Silva Brito; Mario Guimarães Junior; Josy Anteveli Osajima Furtini; Luciana de Matos Alves Pinto; Thiago de Paula Protásio; Lourival Marin Mendes; José Benedito Guimarães Junior (Environmental Science and Pollution Research, 2022)

Does the structure of riparian vegetation affect the diversity of macrophytes in eastern amazonian streams? - Rayssa Silva Carmo; Ana Luísa Biondi Lima Fares; Gizelia Ferreira Matos Pereira; Thaisa Sala Michelan (Biologia, 2022)

Microcontaminants Removal in Constructed Wetlands with Different Baffle Arrangements and Cultivated with Pennisetum setaceum - Ana Flávia Santos Rabelo de Melo; Jacineumo Falcão de Oliveira; Fátima Resende Luiz Fia; Ronaldo Fia; Mateus Pimentel de Matos; Ananda Lima Sanson (Water, Air, & Soil Pollution, 2022)

Aneuploids and its increment on diversity of Lippia alba polyploid complex: genetic aspects and origin - Juliana Mainenti Leal Lopes; Victória Rabelo Campos; Aryane Campos Reis; Elyabe Monteiro de Matos; Ana Luisa Sousa Azevedo; Marco Antonio Machado; Richard Michael Grazul; Lyderson Facio Viccini (Molecular Biology Reports, 2022)

Effects of different probiotic strains B. lactis, L. rhamnosus and L. reuteri on brain-intestinal axis immunomodulation in an endotoxin-induced inflammation - Monique Michels; Gabriel Fernandes Alves Jesus; Mariane Rocha Abatti; Emily Córneo; Luana Cucker; Heloisa de Medeiros Borges; Natan da Silva Matos; Luana Bezerra Rocha; Rodrigo Dias; Carla Sasso Simon; Ana Paula Lorenzen Voytena; Marina Rossetto; et al. (Molecular Neurobiology, 2022)

Treatment of Wastewater Containing New and Non-biodegradable Textile Dyes: Efficacy of Combined Advanced Oxidation and Adsorption Processes - Ana J. Feuzer-Matos; Renan C. Testolin; Wendell Pimentel-Almeida; Ramaiana Radetski-Silva; Maria J. Deomar-Simões; Letícia Poyer-Radetski; Rafael Ariente-Neto; Marina J. Batista-Barwinski; Cleder A. Somensi; Claudemir M. Radetski (Water, Air, & Soil Pollution, 2022)

Hesperetin-Based Hydrogels Protect the Skin against UV Radiation-Induced Damage - Tatianny de Araújo Andrade; Luana Heimfarth; Danillo Menezes dos Santos; Márcio Roberto Viana dos Santos; Ricardo Luiz Cavalcanti de Albuquerque-Júnior; Agenor Gomes dos Santos-Neto; Guilherme Rodolfo Souza de Araujo; Ana Amélia Moreira Lira; Saulo Santos Matos; Luiza Abrahão Frank; Thallita Kelly Rabelo; Lucindo José Quintans-Júnior; et al. (AAPS PharmSciTech, 2022)

SARS-CoV-2 seroprevalence in Portugal following the third epidemic wave: results of the second National Serological Survey (ISN2COVID-19) - Irina Kislaya; Paulo Gonçalves; Verónica Gómez; Vânia Gaio; Rita Roquette; Marta Barreto; Mafalda Sousa-Uva; Ana Rita Torres; Joana Santos; Rita Matos; Carla Manita; João Almeida Santos; et al. (Infectious Diseases, 2022)

Population structure and intraspecific ecological niche differentiation point to lineage divergence promoted by polyploidization in Psidium cattleyanum (Myrtaceae) - Raquel Moura Machado; Fernanda Ancelmo de Oliveira; Ana Carolina Devides Castello; Fábio de Matos Alves; Anete Pereira de Souza; Eliana Regina Forni-Martins (Tree Genetics & Genomes, 2022)

Rhizobacteria from Brazilian semiarid biome as growth promoters of soybean (Glycine max L.) under low water availability - Ana Paula Andrade Braga; Jaqueline Matos Cruz; Itamar Soares de Melo (Brazilian Journal of Microbiology, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Foraging costs drive within-colony spatial segregation in shearwaters from two contrasting environments in the North Atlantic Ocean - Jorge M. Pereira; Jaime A. Ramos; Nathalie Almeida; Pedro M. Araújo; Filipe R. Ceia; Pedro Geraldes; Ana M. Marques; Diana M. Matos; Isabel Rodrigues; Ivo dos Santos; Vitor H. Paiva (Oecologia, 2022)

Insecticidal activity of copper (II) complexes with flavanone derivatives - André Lucio Franceschini Sarria; Andréia Pereira Matos; Ana Carolina Volante; Antônio Rogério Bernardo; Gracielle Oliveira Sabbag Cunha; João Batista Fernandes; Moacir Rossi Forim; Paulo Cezar Vieira; Maria Fátima das Graças Fernandes da Silva (Natural Product Research, 2022)

Bioaerosol vertical fungal spores profile in Minas Gerais State, Brazil - Ana Paula Mendes Emygdio; Cristiane Degobbi; Federico Carotenuto; Dulcilena de Matos Castro e Silva; Thaysla Beluco Quintino; Rafael Henrique de Souza Zanetti; Mauricio C. Mantoani; Solana Meneghel Boschilia; Lara Chaves Carvalho Guerra; Pedro Leite da Silva Dias; Cindy E. Morris; Fábio Luiz Teixeira Gonçalves (Aerobiologia, 2022)

Nisin Induces Cell-Cycle Arrest in Free-Living Amoebae Acanthamoeba castellanii - Marianna de Carvalho Clímaco; Yrna Lorena Matos de Oliveira; Anne Caroline Santos Ramos; Jucicleide Ramos-de-Souza; Audrey Rouse Soares Tavares Silva; Sona Jain; Marilise Brittes Rott; Ricardo Scher; Cristiane Bani Correa; Ana Andrea Teixeira Barbosa; Silvio Santana Dolabella (Acta Parasitologica, 2022)

Constructed Wetlands in the Production of Crimson Fountain Grass Flower Stems - Iracema Clara Alves Luz; Antonio Rodrigues da Cunha Neto; Ana Flávia Santos Rabelo de Melo; Michele Valquíria dos Reis; Fátima Resende Luiz Fia; Mateus Pimentel de Matos; Patrícia Duarte de Oliveira Paiva (Water, Air, & Soil Pollution, 2022)

Swine influenza A virus subtypes circulating in Brazilian commercial pig herds from 2012 to 2019 - Ana Luiza Soares Fraiha; Ana Carolina Diniz Matos; João Luis Reis Cunha; Beatriz Senra Álvares da Silva Santos; Maria Vitória Chaves Peixoto; Anna Gabriella Guimarães Oliveira; Grazielle Cossenzo Florentino Galinari; Heloíza Irtes de Jesus Nascimento; Maria Isabel Maldonado Coelho Guedes; Alexandre de Magalhães Vieira Machado; Erica Azevedo Costa; Zélia Inês Portela Lobato (Brazilian Journal of Microbiology, 2021)

Styrylpyrone, isolated from an Amazon plant, induces cell cycle arrest and autophagy in Leishmania amazonensis - Nilma de Souza Fernandes; Vânia Cristina Desoti; Alcilene Dias; Yasmin Cunha da Silva; Ana Paula de Azevedo dos Santos; Guilherme Matos Passarini; Celso Vataru Nakamura; Valdir Florêncio da Veiga Junior (Natural Product Research, 2021)

Key Constituents and Antioxidant Activity of Novel Functional Foods Developed with Skeletonema Sp. Biomass - Inês Guarda; Inês Fonseca; Hugo Pereira; Luisa Louro Martins; Romina Gomes; Joana Matos; Ana Gomes-Bispo; Narcisa Maria Bandarra; Cláudia Afonso; Carlos Cardoso (Journal of Aquatic Food Product Technology, 2021)

Using textile industrial sludge, sewage wastewater, and sewage sludge as inoculum to degrade recalcitrant textile dyes in a co-composting process: an assessment of biodegradation efficiency and compost phytotoxicity - Renan C. Testolin; Ana Júlia Feuzer-Matos; Sylvie Cotelle; Fabrizio Adani; Leandro Janke; Gabriel Poyer-Radetski; Antonio C. Pereira; Rafael Ariente-Neto; Cleder A. Somensi; Claudemir M. Radetski (Environmental Science and Pollution Research, 2021)

Ecoengineering Solutions for the Impairment of Spreading and Growth of Invasive Spartina patens in Mediterranean Salt Marshes - Ricardo Cruz de Carvalho; Eduardo Feijão; Irina Duarte; Vanessa Pinto; Marisa Silva; Ana Rita Matos; Anabela Bernardes da Silva; Isabel Caçador; Patrick Reis-Santos; Vanessa F. Fonseca; Bernardo Duarte (Frontiers in Marine Science, 2021)
The invasion of natural communities by non-indigenous species represents one of the most serious threats to biodiversity. Understanding the ecophysiology of invasive species can provide insights into potential physiological handicaps relative to native species. By doing so, we can leverage the development of ecoengineering solutions for the removal of non-indigenous species, preferably using non-chemical methods. Spartina patens is a known invasive species of cordgrass aggressively proliferating in Mediterranean salt marshes, producing impenetrable monospecific stands. As its occurrence is delimited by the upper high tide water level, we hypothesized that S. patens is intolerant to waterlogging. Therefore, we developed a field experiment where strands of S. patens were kept waterlogged over the entire tidal cycle for 30 days. At the end of the experimental period, plants in the trial plots exhibited severe stress symptoms at different physiological levels compared with control plots (no intervention). At the photobiological level, intervened plants exhibited lower efficiency in producing chemical energy from light, whilst at the biochemical level waterlogging impaired the antioxidant system and increased lipid peroxidation products. Furthermore, the application of chlorophyll a pulse amplitude modulated (PAM) fluorometry, a non-invasive technique, allowed us to evaluate the effectiveness of the implemented measures, being the tool that provided the best separation between the control and intervened population. Considering the physiological traits observed here, ecoengineering solutions based on increased waterlogging of S. patens stands, can be a low-cost and efficient measure to reduce the spreading and growth of this invasive species in the Mediterranean and other salt marshes worldwide with little disturbance.

Shining light on anther culture, a poorly understood regeneration route in passion fruit (Passiflora gibertii N. E. Brown): histological, hormonal, and phytochemical aspects - Wellington dos Santos Soares; Cláudio Horst Bruckner; Ana Cláudia Ferreira da Cruz; Diego Ismael Rocha; Elyabe Monteiro de Matos; Andréa Dias Koehler; Lyderson Facio Viccini; Wagner Campos Otoni (In Vitro Cellular & Developmental Biology - Plant, 2021)

The hidden curve behind COVID-19 outbreak: the impact of delay in treatment initiation in cancer patients and how to mitigate the additional risk of dying—the head and neck cancer model - Leandro L. Matos; Carlos Henrique Q. Forster; Gustavo N. Marta; Gilberto Castro Junior; John A. Ridge; Daisy Hirata; Adalberto Miranda-Filho; Ali Hosny; Alvaro Sanabria; Vincent Gregoire; Snehal G. Patel; Johannes J. Fagan; et al. (Cancer Causes & Control, 2021)

Toxicity Going Nano: Ionic Versus Engineered Cu Nanoparticles Impacts on the Physiological Fitness of the Model Diatom Phaeodactylum tricornutum - Marco Franzitta; Eduardo Feijão; Maria Teresa Cabrita; Carla Gameiro; Ana Rita Matos; João Carlos Marques; Johannes W. Goessling; Patrick Reis-Santos; Vanessa F. Fonseca; Carlo Pretti; Isabel Caçador; Bernardo Duarte (Frontiers in Marine Science, 2020)
Increasing input of Metal Engineered Nano Particles (MeENPs) in marine ecosystems has raised concerns about their potential toxicity on phytoplankton. Given the lack of knowledge on MeENPs impact on these important primary producers, the effects of Copper Oxide (CuO) ENPs on growth, physiology, pigment profiles, fatty acid (FA) metabolism, and oxidative stress were investigated in the model diatom Pheodactylum tricornutum , to provide suitable biomarkers of CuO ENP exposure versus its ionic counterpart. Diatom growth was inhibited by CuO ENPs but not Ionic Cu, suggesting CuO ENP cytotoxicity. Pulse Modulated Amplitude (PAM) phenotyping evidenced a decrease in the electron transport energy flux, pointing to a reduction in chemical energy generation following CuO ENPs exposure, as well as an increase in the content of the non-functional Cu-substituted chlorophyll a (CuChl a ). A significant decrease in eicosapentaenoic acid (C20:5) associated with a significant rise in thylakoid membranes FAs reflected the activation of counteractive measures to photosynthetic impairment. Significant increase in the omega 6/omega 3 ratio, underline expectable negative repercussions to marine food webs. Increased thiobarbituric acid reactive substances reflected heightened oxidative stress by CuO ENP. Enhanced Glutathione Reductase and Ascorbate Peroxidase activity were also more evident for CuO ENPs than ionic Cu. Overall, observed molecular changes highlighted a battery of possible suitable biomarkers to efficiently determine the harmful effects of CuO ENPs. The results suggest that the occurrence and contamination of these new forms of metal contaminants can impose added stress to the marine diatom community, which could have significant impacts on marine ecosystems, namely through a reduction of the primary productivity, oxygen production and omega 6 production, all essential to sustain heterotrophic marine life.

Otoliths-composed gelatin/sodium alginate scaffolds for bone regeneration - Daisy Pereira Valido; Wilson Déda Gonçalves Júnior; Maria Eliane de Andrade; Allan Andrade Rezende; Felipe Mendes de Andrade de Carvalho; Renata de Lima; Gabriela das Graças Gomes Trindade; Caio de Alcântara Campos; Ana Maria Santos Oliveira; Eloísa Portugal Barros Silva Soares de Souza; Luiza Abrahão Frank; Silvia Stanisçuaski Guterres; et al. (Drug Delivery and Translational Research, 2020)

Development, characterization, and anti-leishmanial activity of topical amphotericin B nanoemulsions - Ana Paula dos Santos Matos; Deise Cristina Drummond Xavier Paes Lopes; Maria Luíza Honório Peixoto; Veronica da Silva Cardoso; Alane Beatriz Vermelho; Ralph Santos-Oliveira; Alessandra Lifsitch Viçosa; Carla Holandino; Eduardo Ricci-Júnior (Drug Delivery and Translational Research, 2020)

Detection of anti-Pneumocystis jirovecii antibodies in human serum using a recombinant synthetic multi-epitope kexin-based antigen - Ana Luísa Tomás; Fernando Cardoso; Bruno de Sousa; Olga Matos (European Journal of Clinical Microbiology & Infectious Diseases, 2020)
Interest in the detection of specific anti- Pneumocystis jirovecii antibodies has emerged as less-invasive alternative diagnostic approaches. Here is presented the performance of an ELISA based on a recombinant synthetic multi-epitope kexin 1 (Kex1) antigen of P. jirovecii , previously developed. Results showed that IgM anti-Kex1 levels were found significantly increased in patients with Pneumocystis pneumonia (PcP) compared with non-PcP cases ( p < 0.001), allowing a diagnostic performance of PcP with a 70.8% sensitivity and a 75.0% specificity. These results suggest that this Kex1-based ELISA is a promising tool toward the serodiagnosis of PcP when the standard methods are difficult to perform.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

The Impact of Atmospheric Correction on Brazilian Earth Tide Models - Daniel Arana; Paulo de Oliveira Camargo; Eder Cassola Molina; Denizar Blitzkow; Ana Cristina Oliveira Cancoro de Matos; Jean Paul Boy (Pure and Applied Geophysics, 2020)

Development of microsatellite markers for Lippia alba and related Lippia species - Juliana Mainenti Leal Lopes; Elyabe Monteiro de Matos; Cristiane Zorzatto; Ana Luisa Sousa Azevedo; Marco Antonio Machado; Michael Chester; Lyderson Facio Viccini (Molecular Biology Reports, 2020)

Seasonal variations in the diversity and structure of decapod communities in the changing hydrological scenario of the northwest African upwelling - Sidi M. Mohamed Moctar; Ana Ramos; Susana S. de Matos-Pita; Fran Ramil; Jens-Otto Krakstad (Marine Biodiversity, 2020)

Fruits and vegetable-processing waste: a case study in two markets at Rio de Janeiro, RJ, Brazil - Talita Braga de Brito Nogueira; Tatiana Pereira Matos da Silva; Daniel de Araújo Luiz; Cristiano José de Andrade; Lidiane Maria de Andrade; Mariana Simões Larraz Ferreira; Ana Elizabeth Cavalcante Fai (Environmental Science and Pollution Research, 2020)

Somatic embryogenesis induced from vascular tissues in leaf explants of Lisianthus (Eustoma grandiflorum (Raf.) Shinn) generates true-to-type diploid plants - Maria Yumbla-Orbes; Diego Ismael Rocha; Elyabe Monteiro de Matos; Andréa Dias Koehler; Marcos Vinicius Marques Pinheiro; Diego Silva Batista; Débora Márcia Silva Freitas; Ana Claudia Ferreira da Cruz; José Geraldo Barbosa; Lyderson Facio Viccini; Wagner Campos Otoni (Vegetos, 2020)

Morphophysiology of forage peanut submitted to different intensities of defoliation on grazing with sheep - Olmar Antônio Denardin Costa; Otoniel Geter Lauz Ferreira; Douglas Sampaio Henrique; Ricardo Zambarda Vaz; Ana Carolina Fluck; Wagner Paris; Alexsandro Bahr Kröning; Luis Alberto Alonzo Griffith; Oscar Ivan Tuz Matos (Tropical Animal Health and Production, 2020)

Fatty acid amide hydrolase inhibition normalises bladder function and reduces pain through normalising the anandamide/palmitoylethanolamine ratio in the inflamed bladder of rats - Ana Charrua; Rita Matos; Raquel Oliveira; Tim Marczylo; Istvan Nagy; Francisco Cruz (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Assessing the ecological status of fluvial ecosystems employing a macroinvertebrate multi-taxon and multi-biomarker approach - Carolina Rodrigues; Ana Bio; Laura Guimarães; Virgínia C. Fernandes; Cristina Delerue-Matos; Natividade Vieira (Environmental Monitoring and Assessment, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Evaluation of the seaweeds Chondrus crispus and Ulva lactuca as functional ingredients in gilthead seabream (Sparus aurata) - Inês Guerreiro; Rui Magalhães; Filipe Coutinho; Ana Couto; Sara Sousa; Cristina Delerue-Matos; Valentina F. Domingues; Aires Oliva-Teles; Helena Peres (Journal of Applied Phycology, 2019)

The digestive tube of Piaractus brachypomus : gross morphology, histology/histochemistry of the mucosal layer and the effects of parasitism by Neoechinorhynchus sp. - Maria I. B. de Oliveira; Lorena V. de Matos; Lídia A. da Silva; Edsandra C. Chagas; Grazyelle S. da Silva; Ana L. S. Gomes (Journal of Fish Biology, 2019)
The objective of the present study was to describe the histology and histochemistry of the mucosal layer of the digestive tube of Piaractus brachypomus , and the histopathology associated with parasitism by Neoechinorhynchus sp. The digestive tube of P. brachypomus consists of three macroscopically distinct portions: short, rectilinear and elastic‐walled ooesophagus, J‐shaped siphon stomach and a long intestine with rectilinear and curved portions, defined by patterns of villi as foregut, midgut, and hindgut. Histological and histochemical differences were observed in the mucosal layers of the different digestive tube regions, such as intense production of neutral and acidic mucous substances in the pseudostratified mucosal epithelium of the oesophagus; positive periodic acid Schiff reagent (PAS)reactions at the apex of the columnar epithelial cells of the stomach and increased intensity of histochemical reactions in the hindgut region. Neoechinorhynchus sp. was present in 85.7% of specimens examined, with a mean intensity of 7.4 ± 6.2 (±) and abundance of 6.33. Good health of the fish indicated by high relative condition factor values ( Kn ) and occurrence of only mild to moderate alteration in the mucosal layer indicated that Neoechinorhynchus sp. exhibits low pathogenicity towards P. brachypomus hosts in farming environments, with low levels of infection.

Chronic Metabolic Derangement-Induced Cognitive Deficits and Neurotoxicity Are Associated with REST Inactivation - Aline Pertile Remor; Rodrigo Augusto da Silva; Filipe José de Matos; Viviane Glaser; Roberta de Paula Martins; Karina Ghisoni; Débora da Luz Scheffer; Denise Carleto Andia; Daniele Portinho; Ana Paula de Souza; Paulo Alexandre de Oliveira; Rui Daniel Prediger; et al. (Molecular Neurobiology, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

Shotgun proteomics of ascidians tunic shed light into the interaction between host and their associated bacteria - Ana Matos; Dany Domínguez-Pérez; Daniela Almeida; Alexandre Campos; Hugo Osório; Vitor Vasconcelos; Agostinho Antunes (Frontiers in Marine Science, 2019)

Medusozoa in Portugal: impact on the ecosystems and development of DNA-based tools for the early forecasting of mass occurrences - Tomás Rodrigues; Ana Matos; Dany Domínguez-Pérez; Joana Falcão; Sónia Marques; Sérgio Leandro; Daniela Almeida; Agostinho Antunes (Frontiers in Marine Science, 2019)

Polymerase chain reaction as a promising tool for DNA-based diet studies of crustaceans - Joana Campos; Cristiana Moreira; Sérgia Costa-Dias; Eunice Ferreira; Ana Matos; Vitor Vasconcelos; Agostinho Antunes (Frontiers in Marine Science, 2019)

Medusozoa in Portugal: impact on the ecosystems and development of DNA-based tools for the early forecasting of mass occurrences - Tomás Rodrigues; Ana Matos; Dany Domínguez-Pérez; Joana Falcão; Sónia Marques; Sérgio Leandro; Daniela Almeida; Agostinho Antunes (Frontiers in Marine Science, 2019)

Effects of heat stress in the leaf mitotic cell cycle and chromosomes of four wine-producing grapevine varieties - Ana Carvalho; Fernanda Leal; Manuela Matos; José Lima-Brito (Protoplasma, 2018)

Creation of a coastal evolution prognostic model using shoreline historical data and techniques of digital image processing in a GIS environment for generating future scenarios - Willamys R. N. de Sousa; Michael V. S. Souto; Stefanny S. Matos; Cynthia R. Duarte; Ana R. G. N. L. Salgueiro; Cláudio A. da Silva Neto (International Journal of Remote Sensing, 2018)

Climate Change Impacts on Seagrass Meadows and Macroalgal Forests: An Integrative Perspective on Acclimation and Adaptation Potential - Bernardo Duarte; Irene Martins; Rui Rosa; Ana R. Matos; Michael Y. Roleda; Thorsten B. H. Reusch; Aschwin H. Engelen; Ester A. Serrão; Gareth A. Pearson; João C. Marques; Isabel Caçador; Carlos M. Duarte; et al. (Frontiers in Marine Science, 2018)

Ectomycorrhizal inoculation with Pisolithus tinctorius reduces stress induced by drought in cork oak - Mónica Sebastiana; Anabela Bernardes da Silva; Ana Rita Matos; André Alcântara; Susana Silvestre; Rui Malhó (Mycorrhiza, 2018)

High responsiveness in de novo shoot organogenesis induction of Passiflora cristalina (Passifloraceae), a wild Amazonian passion fruit species - Rodrigo Brito de Faria; Ilio Fealho de Carvalho; Ana Aparecida Bandini Rossi; Elyabe Monteiro de Matos; Diego Ismael Rocha; Daniela Lopes Paim Pinto; Wagner Campos Otoni; Maurecilne Lemes da Silva (In Vitro Cellular & Developmental Biology - Plant, 2018)

Newcumber: Advances towards the sustainable rearing of sea cucumbers - Pedro Félix; Ana Pombo; Francisco Azevedo E Silva; Tomás Simões; João Sousa; Eliana Venâncio; Luís Narciso; Ana Amorim; Ricardo Melo; Ana Rita Matos; Anabela Silva; Tiago Marques; et al. (Frontiers in Marine Science, 2018)

Hg-Planktarctic - Unravelling the metabolic adaptations in phytoplankton continuously exposed to volcanic-mercury in Deception Island waters (Antarctica) - Bernardo Duarte; Carlos Cordeiro; Marta Sousa Silva; Andreia Figueiredo; Rui Rosa; João Canário; Isabel Caçador; João Marques; Maria Teresa Cabrita; Ana Rita Matos; Carla Gameiro (Frontiers in Marine Science, 2018)

Unlocking the hidden nutritional value of Portuguese edible halophytes cultivated under estuarine water irrigation schemes - Filipa Antunes; Bernardo Duarte; Márcia Pinto; Anabela Silva; Ana Rita Matos; Isabel Caçador; Carlos Brandão (Frontiers in Marine Science, 2018)

Study of the removal mechanism of aquatic emergent pollutants by new bio-based chars - Maria Manuel Serrano Bernardo; Catarina Alexandra Catanas Madeira; Nuno Carlos Lapa dos Santos Nunes; Diogo André Costa Messias Dias; Delfina Maria Barbosa Godinho; Maria Filomena de Jesus Pinto; Inês Alexandra Morgado do Nascimento Matos; Ana Paula Batista Carvalho; Isabel Maria de Figueiredo Ligeiro Fonseca (Environmental Science and Pollution Research, 2017)

Morpho-histological, histochemical, and molecular evidences related to cellular reprogramming during somatic embryogenesis of the model grass Brachypodium distachyon - Evelyn Jardim Oliveira; Andréa Dias Koehler; Diego Ismael Rocha; Lorena Melo Vieira; Marcos Vinícius Marques Pinheiro; Elyabe Monteiro de Matos; Ana Claudia Ferreira da Cruz; Thais Cristina Ribeiro da Silva; Francisco André Ossamu Tanaka; Fabio Tebaldi Silveira Nogueira; Wagner Campos Otoni (Protoplasma, 2017)

In Silico, In Vitro and In Vivo Toxicological Assessment of BPP-BrachyNH2, A Vasoactive Proline-Rich Oligopeptide from Brachycephalus ephippium - Daniel D. R. Arcanjo; Ana Carolina Mafud; Andreanne G. Vasconcelos; José Couras da Silva-Filho; Maurício P. M. Amaral; Lucas M. Brito; Marcelo P. Bemquerer; Selma A. S. Kückelhaus; Alexandra Plácido; Cristina Delerue-Matos; Nuno Vale; Yvonne P. Mascarenhas; et al. (International Journal of Peptide Research and Therapeutics, 2017)

The water avoidance stress induces bladder pain due to a prolonged alpha1A adrenoceptor stimulation - Rita Matos; Paula Serrão; Larissa Rodriguez; Lori Ann Birder; Francisco Cruz; Ana Charrua (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Cytotoxicity and genotoxicity of Guaribas river water (Piauí, Brazil), influenced by anthropogenic action - João Marcelo de Castro e Sousa; Ana Paula Peron; Louridânya da Silva e Sousa; Mércia de Moura Holanda; Ataíde de Macedo Vieira Lima; Vitor Alves de Oliveira; Felipe Cavalcanti Carneiro da Silva; Leonardo Henrique Guedes de Morais Lima; Leomá Albuquerque Matos; Sandra Maria Mendes de Moura Dantas; Raí Pablo Sousa de Aguiar; Muhammad Torequl Islam; et al. (Environmental Monitoring and Assessment, 2017)

Variation in stem mortality rates determines patterns of above‐ground biomass in A mazonian forests: implications for dynamic global vegetation models - Michelle O. Johnson; David Galbraith; Manuel Gloor; Hannes De Deurwaerder; Matthieu Guimberteau; Anja Rammig; Kirsten Thonicke; Hans Verbeeck; Celso von Randow; Abel Monteagudo; Oliver L. Phillips; Roel J. W. Brienen; et al. (Global Change Biology, 2016)
Understanding the processes that determine above‐ground biomass ( AGB ) in Amazonian forests is important for predicting the sensitivity of these ecosystems to environmental change and for designing and evaluating dynamic global vegetation models ( DGVM s). AGB is determined by inputs from woody productivity [woody net primary productivity ( NPP )] and the rate at which carbon is lost through tree mortality. Here, we test whether two direct metrics of tree mortality (the absolute rate of woody biomass loss and the rate of stem mortality) and/or woody NPP , control variation in AGB among 167 plots in intact forest across Amazonia. We then compare these relationships and the observed variation in AGB and woody NPP with the predictions of four DGVM s. The observations show that stem mortality rates, rather than absolute rates of woody biomass loss, are the most important predictor of AGB , which is consistent with the importance of stand size structure for determining spatial variation in AGB . The relationship between stem mortality rates and AGB varies among different regions of Amazonia, indicating that variation in wood density and height/diameter relationships also influences AGB . In contrast to previous findings, we find that woody NPP is not correlated with stem mortality rates and is weakly positively correlated with AGB . Across the four models, basin‐wide average AGB is similar to the mean of the observations. However, the models consistently overestimate woody NPP and poorly represent the spatial patterns of both AGB and woody NPP estimated using plot data. In marked contrast to the observations, DGVM s typically show strong positive relationships between woody NPP and AGB . Resolving these differences will require incorporating forest size structure, mechanistic models of stem mortality and variation in functional composition in DGVM s.

Chemical composition and anti-inflammatory activity of the leaves of Byrsonima verbascifolia - Aline Aparecida Saldanha; Lucas Fernandes do Carmo; Sara Batista do Nascimento; Natália Alves de Matos; Clarice de Carvalho Veloso; Ana Hortência Fonsêca Castro; Ric C. H. De Vos; André Klein; João Máximo de Siqueira; Carlos Alexandre Carollo; Thalita Vieira do Nascimento; Mônica Cristina Toffoli-Kadri; et al. (Journal of Natural Medicines, 2016)

Adaptive Gene Loss? Tracing Back the Pseudogenization of the Rabbit CCL8 Chemokine - Wessel van der Loo; Maria João Magalhaes; Ana Lemos de Matos; Joana Abrantes; Fumio Yamada; Pedro J. Esteves (Journal of Molecular Evolution, 2016)

An overview of the lagomorph immune system and its genetic diversity - Ana Pinheiro; Fabiana Neves; Ana Lemos de Matos; Joana Abrantes; Wessel van der Loo; Rose Mage; Pedro José Esteves (Immunogenetics, 2016)

Biodiversity of Decapoda in Guinea-Bissau waters. - De Jesús Nair; Ramil Fran; Ramos Ana; De Matos-Pita Susana S. (Frontiers in Marine Science, 2016)

Contribution to the knowledge of the decapod fauna from Cabo Verde Islands - Neves Keider; Soto De Matos-Pita Susana; Ramil Fran; Ramos Ana (Frontiers in Marine Science, 2016)

Effects of nickel on the fatty acid composition of the diatom Phaeodactylum tricornutum - Matos Ana Rita; Gameiro Carla; Duarte Bernardo; Caçador Isabel; Cabrita Maria Teresa (Frontiers in Marine Science, 2016)

Biochemical and biophysical tools for the detection of trace metal stress in the diatom model species Phaeodactylum tricornutum - Cabrita Maria Teresa; Duarte Bernardo; Gameiro Carla; Utkin Andrei; Matos Ana Rita; Caçador Isabel; Cartaxana Paulo (Frontiers in Marine Science, 2016)

Western European Wild and Landraces Hazelnuts Evaluated by SSR Markers - Sandra Martins; Fernanda Simões; Diogo Mendonça; José Matos; Ana Paula Silva; Valdemar Carnide (Plant Molecular Biology Reporter, 2015)

Synthesis, characterization, cytotoxic and antitubercular activities of new gold(I) and gold(III) complexes containing ligands derived from carbohydrates - Joana Darc Souza Chaves; Jaqueline Lopes Damasceno; Marcela Cristina Ferreira Paula; Pollyanna Francielli de Oliveira; Gustavo Chevitarese Azevedo; Renato Camargo Matos; Maria Cristina S. Lourenço; Denise Crispim Tavares; Heveline Silva; Ana Paula Soares Fontes; Mauro Vieira de Almeida (BioMetals, 2015)

Vitrified sheep isolated secondary follicles are able to grow and form antrum after a short period of in vitro culture - Franciele Osmarini Lunardi; Roberta Nogueira Chaves; Laritza Ferreira de Lima; Valdevane Rocha Araújo; Ivina Rocha Brito; Carlos Eduardo Azevedo Souza; Mariana Aragão Matos Donato; Christina Alves Peixoto; Andras Dinnyes; Cláudio Cabral Campello; José Ricardo de Figueiredo; Ana Paula Ribeiro Rodrigues (Cell and Tissue Research, 2015)

Toxicity Identification Evaluation (Phase I) of water and sediment samples from a tropical reservoir contaminated with industrial and domestic effluents - Mariana de F Matos; Clarice Maria Rispoli Botta; Ana Lúcia Fonseca (Environmental Monitoring and Assessment, 2014)

Effects of Ezetimibe on Endothelial Progenitor Cells and Microparticles in High-Risk Patients - Lívia Campos Amaral Lins; Carolina Nunes França; Francisco Antonio Helfenstein Fonseca; Simone Pinto Melo Barbosa; Lívia Nascimento Matos; Ana Carolina Aguirre; Henrique Tria Bianco; Jonatas Bussador do Amaral; Maria Cristina Izar (Cell Biochemistry and Biophysics, 2014)

Genetic relationship among wild, landraces and cultivars of hazelnut (Corylus avellana) from Portugal revealed through ISSR and AFLP markers - Sandra Martins; Fernanda Simões; José Matos; Ana Paula Silva; Valdemar Carnide (Plant Systematics and Evolution, 2014)

Tadalafil-induced improvement in left ventricular diastolic function in resistant hypertension - Rodrigo C. Santos; Ana Paula C. de Faria; Natália R. Barbaro; Rodrigo Modolo; Silvia E. Ferreira-Melo; José R. Matos-Souza; Otávio R. Coelho; Juan C. Yugar-Toledo; Vanessa Fontana; David Calhoun; Heitor Moreno (European Journal of Clinical Pharmacology, 2014)

Evolution of viral sensing RIG-I-like receptor genes in Leporidae genera Oryctolagus, Sylvilagus, and Lepus - Ana Lemos de Matos; Grant McFadden; Pedro J. Esteves (Immunogenetics, 2014)

A physiological study of integument secretions in the marine polychaete Eulalia viridis and their potential biotechnological value. - Rodrigo Ana; Alves De Matos António; Carrapiço Francisco; Costa Maria; Costa Pedro (Frontiers in Marine Science, 2014)

Characterization of an insect-specific flavivirus (OCFVPT) co-isolated from Ochlerotatus caspius collected in southern Portugal along with a putative new Negev-like virus - Daniela Duque Ferreira; Shelley Cook; Ângela Lopes; António Pedro de Matos; Aida Esteves; Ana Abecasis; António Paulo Gouveia de Almeida; João Piedade; Ricardo Parreira (Virus Genes, 2013)

Environmental impacts of end-of-life vehicles’ management: recovery versus elimination - Ana Sofia Fonseca; Maria Isabel Nunes; Manuel Arlindo Matos; Ana Paula Gomes (The International Journal of Life Cycle Assessment, 2013)

Integration of beach hydrodynamic and morphodynamic modelling in a GIS environment - Ana Maria Almeida Nobre Silva; Rui Pires Matos Taborda (Journal of Coastal Conservation, 2013)

Changes in natural killer cell subpopulations over a winter training season in elite swimmers - Luís Rama; Ana Maria Teixeira; Alice Matos; Grasiely Borges; Ana Henriques; Michael Gleeson; Susana Pedreiro; Edith Filaire; Francisco Alves; Artur Paiva (European Journal of Applied Physiology, 2013)

Aluminum and sulphate removal by a highly Al-resistant dissimilatory sulphate-reducing bacteria community - Mónica Martins; Rita Taborda; Gonçalo Silva; Ana Assunção; António Pedro Matos; Maria Clara Costa (Biodegradation, 2012)

Diet and the risk of head and neck cancer: a pooled analysis in the INHANCE consortium - Shu-Chun Chuang; Mazda Jenab; Julia E. Heck; Cristina Bosetti; Renato Talamini; Keitaro Matsuo; Xavier Castellsague; Silvia Franceschi; Rolando Herrero; Deborah M. Winn; Carlo La Vecchia; Hal Morgenstern; et al. (Cancer Causes & Control, 2012)

An examination of male and female odds ratios by BMI, cigarette smoking, and alcohol consumption for cancers of the oral cavity, pharynx, and larynx in pooled data from 15 case–control studies - Jay H. Lubin; Joshua Muscat; Mia M. Gaudet; Andrew F. Olshan; Maria Paula Curado; Luigino Dal Maso; Victor Wünsch-Filho; Erich M. Sturgis; Neonilia Szeszenia-Dabrowska; Xavier Castellsague; Zuo-Feng Zhang; Elaine Smith; et al. (Cancer Causes & Control, 2011)

Steady-state level of epidermal growth factor (EGF) mRNA and effect of EGF on in vitro culture of caprine preantral follicles - Juliana Jales H. Celestino; Jamily B. Bruno; Márcia Viviane A. Saraiva; Rebeca M. P. Rocha; Ivina R. Brito; Ana Beatriz G. Duarte; Valdevane R. Araújo; Cleidson M. G. Silva; Maria Helena T. Matos; Claudio C. Campello; José Roberto V. Silva; José Ricardo Figueiredo (Cell and Tissue Research, 2011)

Using zeta-potential measurements to quantify peptide partition to lipid membranes - João M. Freire; Marco M. Domingues; Joana Matos; Manuel N. Melo; Ana Salomé Veiga; Nuno C. Santos; Miguel A. R. B. Castanho (European Biophysics Journal, 2011)

Molecular insight into the population structure of common and spotted dolphins inhabiting the pelagic waters of the Northeast Atlantic - Sophie Quérouil; Luís Freitas; Irma Cascão; Filipe Alves; Ana Dinis; Joana R. Almeida; Rui Prieto; Silvia Borràs; José A. Matos; Diogo Mendonça; Ricardo S. Santos (Marine Biology, 2010)

Playing Darwin. Part B. 20 years of domestication in Drosophila subobscura - Marta Santos; Inês Fragata; Josiane Santos; Pedro Simões; Ana Marques; Margarida Lima; Margarida Matos (Theory in Biosciences, 2010)

SacRALF1, a peptide signal from the grass sugarcane (Saccharum spp.), is potentially involved in the regulation of tissue expansion - Fabiana B. Mingossi; Juliana L. Matos; Ana Paula Rizzato; Ane H. Medeiros; Maria C. Falco; Marcio C. Silva-Filho; Daniel S. Moura (Plant Molecular Biology, 2010)

Sex bias in biopsy samples collected from free-ranging dolphins - Sophie Quérouil; Luís Freitas; Ana Dinis; Filipe Alves; Irma Cascão; Rui Prieto; Mónica A. Silva; Sara Magalhães; José A. Matos; Ricardo S. Santos (European Journal of Wildlife Research, 2010)

Evaluation of metabisulfite and a commercial steel wool for removing chromium(VI) from wastewater - Caio F. Gromboni; George L. Donati; Wladiana O. Matos; Eduardo F. A. Neves; Ana Rita A. Nogueira; Joaquim A. Nóbrega (Environmental Chemistry Letters, 2010)

Bacteria Associated with Toxic Clonal Cultures of the Dinoflagellate Ostreopsis lenticularis - Lumarie Pérez-Guzmán; Ana E. Pérez-Matos; William Rosado; Thomas R. Tosteson; Nadathur S. Govind (Marine Biotechnology, 2008)

Assessing dam implementation impact on threatened carnivores: the case of Alqueva in SE Portugal - Maria J. Santos; Nuno M. Pedroso; Joaquim P. Ferreira; Hugo M. Matos; Teresa Sales-Luís; Íris Pereira; Carla Baltazar; Clara Grilo; Ana T. Cândido; Inês Sousa; Margarida Santos-Reis (Environmental Monitoring and Assessment, 2008)

High gene flow in oceanic bottlenose dolphins (Tursiops truncatus) of the North Atlantic - Sophie Quérouil; Mónica A. Silva; Luís Freitas; Rui Prieto; Sara Magalhães; Ana Dinis; Filipe Alves; José A. Matos; Diogo Mendonça; Philip S. Hammond; Ricardo S. Santos (Conservation Genetics, 2007)

Bacterial diversity associated with the Caribbean tunicate Ecteinascidia turbinata - Ana E. Pérez-Matos; William Rosado; Nadathur S. Govind (Antonie van Leeuwenhoek, 2007)

Cervical cancer and CYP2E1 polymorphisms: implications for molecular epidemiology - Paula M. Ferreira; Raquel Catarino; Deolinda Pereira; Ana Matos; Daniela Pinto; Ana Coelho; Carlos Lopes; Rui Medeiros (European Journal of Clinical Pharmacology, 2006)